CURABLE COMPOSITION FOR IMPRINTS, CURED PRODUCT, METHOD FOR PRODUCING IMPRINT PATTERN, AND METHOD FOR PRODUCING DEVICE

JP7638824B2Active Publication Date: 2025-03-04FUJIFILM CORP
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2021134049
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-08-19
Publication Date
2025-03-04
Estimated Expiration
2041-08-19

AI Technical Summary

Benefits of technology

【0009】 本発明によれば、離型性に優れたインプリント用硬化性組成物、上記インプリント用硬化性組成物の硬化物、上記インプリント用硬化性組成物を用いたインプリントパターンの製造方法、及び、上記インプリントパターンの製造方法を含むデバイスの製造方法が提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007638824000001
    Figure 0007638824000001
  • Figure 0007638824000002
    Figure 0007638824000002
  • Figure 0007638824000003
    Figure 0007638824000003
Patent Text Reader

Abstract

To provide: a curable composition for imprinting, excellent in releasability; a cured product of the curable composition for imprinting; a method for producing an imprint pattern using the curable composition for imprinting; and a method for producing a device, the method including the method for producing an imprint pattern.SOLUTION: There are provided; a curable composition for imprinting, including a polymerizable compound having two or more radical polymerizable groups, a radical polymerization initiator, and at least one compound selected from the group consisting of an organopolysiloxane having only one radical polymerizable group and an organopolysiloxane having no or one radical polymerizable group and having a poly(oxyalkylene) group; a cured product of the curable composition for imprinting; a method for producing an imprint pattern using the curable composition for imprinting; and a method for producing a device, including the method for producing an imprint pattern.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a curable composition for imprints, a cured product, a method for producing an imprint pattern, and a method for producing a device. [Background technology]

[0002] The imprinting method is a technique for transferring a fine pattern onto a material by pressing a metal die (generally called a mold or stamper) on which a pattern has been formed. Since the imprinting method makes it possible to easily create precise fine patterns, it is expected to be applied in various fields in recent years, such as the precision processing field for semiconductor integrated circuits. In particular, nanoimprinting technology, which forms fine patterns at the nano-order level, has attracted attention.

[0003] Patent Document 1 describes a photo-imprinting material that contains (A) a compound having a specific silicone skeleton and (B) a photopolymerization initiator, in which the content of component (B) is 0.5 phr to 30 phr relative to the total mass of component (A). Patent Document 2 describes a curable imprint material that can be used in imprint lithography, the imprint material being made of a mixture of at least one polymerizable main component and at least one polymerizable subcomponent. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2013-65768 A [Patent Document 2] Special table 2016-524330 publication Summary of the Invention [Problem to be solved by the invention]

[0005] As imprinting methods, methods called thermal imprinting and curing imprinting have been proposed based on the transfer method. In thermal imprinting, a mold is pressed into a thermoplastic resin heated to above its glass transition temperature (hereinafter sometimes referred to as "Tg"), and then the mold is released after cooling to form a fine pattern. This method allows the selection of a wide variety of materials, but it also has problems such as the difficulty of forming fine patterns due to the need for high pressure during pressing and reduced dimensional accuracy caused by thermal shrinkage, etc. On the other hand, in the curing imprinting method, for example, a mold is pressed against a curable film formed from the curable composition for imprinting, and then the cured film is photocured or thermally cured, and then the mold is released. Since imprinting is performed on an uncured material, high pressure application and high temperature heating can be omitted in part or in whole, and fine patterns can be easily produced. In addition, since the dimensional change before and after curing is small, there is also an advantage that fine patterns can be formed with high accuracy. Recently, new developments have been reported, such as the nanocasting method, which combines the advantages of both thermal imprinting and curing imprinting, and the reversal imprinting method, which creates three-dimensional layered structures. In the curing type imprinting method, a curable composition for imprinting is applied onto a support (the surface of which is subjected to an adhesion treatment as necessary), and then dried as necessary to form a curable film, and a mold made of a light-transmitting material such as quartz is pressed against the support. With the mold pressed against the support, the curable composition for imprinting is cured by light irradiation or heating, and the mold is then released to produce a cured product to which a desired pattern has been transferred. Methods for applying the curable composition for imprints onto a support include spin coating and inkjet printing. In addition, a method of performing microfabrication using a transferred imprint pattern as a mask is called nanoimprint lithography (NIL), and is being developed as a next-generation lithography technology to replace the current ArF immersion process. For this reason, the curable composition for imprints used in NIL must be capable of resolving ultrafine patterns of 20 nm or less, similar to EUV resists, and must have high etching resistance as a mask when microfabricating a processing target. Specific examples of the curable composition for imprints intended for use as a mask include Japanese Patent No. 5426814, Japanese Patent Publication No. 2015-009171, Japanese Patent Publication No. 2015-185798, Japanese Patent Publication No. 2015-070145, and Japanese Patent Publication No. 2015-128134.

[0006] In the curing type imprinting method, it is required that the force required for peeling the cured product of the curable composition for imprints from the mold be small in order to prevent deformation, breakage, etc. of the cured product. In this specification, when a small force is required to peel the cured product of the curable composition for imprints from a mold, the composition is said to have excellent releasability for the resulting cured product.

[0007] An object of the present invention is to provide a curable composition for imprints having excellent releasability, a cured product of the curable composition for imprints, a method for producing an imprint pattern using the curable composition for imprints, and a method for producing a device including the method for producing an imprint pattern. [Means for solving the problem]

[0008] Representative embodiments of the present invention are described below. <1> Compound A is a polymerizable compound having two or more radical polymerizable groups; Compound B which is a radical polymerization initiator; and compound C, which is at least one selected from the group consisting of organopolysiloxanes having only one radically polymerizable group and no poly(oxyalkylene) group, organopolysiloxanes having only one radically polymerizable group and a poly(oxyalkylene) group, and organopolysiloxanes having no radically polymerizable group and a poly(oxyalkylene) group. Curable composition for imprints. <2> the organopolysiloxane having only one radically polymerizable group and no poly(oxyalkylene) group, and the organopolysiloxane having only one radically polymerizable group and having a poly(oxyalkylene) group, wherein the radically polymerizable group is an acryloyl group or a (meth)acryloyl group; <1> The curable composition for imprints according to claim 1. <3> the number of carbon atoms in the alkylene group in the poly(oxyalkylene) group is 2 or 3; <1> or <2> The curable composition for imprints according to claim 1. <4> The compound C contains a repeating unit represented by the following formula (S-1): <1> ~ <3> 13. The curable composition for imprints according to claim 12, [ka] In formula (S-1), each R independently represents a hydrocarbon group. <5> The above organopolysiloxane having only one radically polymerizable group and having a poly(oxyalkylene) group, and the above organopolysiloxane having no radically polymerizable group and having a poly(oxyalkylene) group, each contain a structural unit represented by the following formula (S-2): <1> ~ <4> 13. The curable composition for imprints according to claim 12, [ka] In formula (S-2), R represents a hydrocarbon group; S1 represents a group having a poly(oxyalkylene) group. <6> The compound B is a photoradical polymerization initiator. <1> ~ <5> 13. The curable composition for imprints according to claim 12, <7> The ratio of the total mass of the compound C to the total mass of the compound A contained in the composition is 0.2 to 20 mass%. <1> ~ <6> 13. The curable composition for imprints according to claim 12, <8> The molar amount of the radical polymerizable group relative to the total solid content of the composition is 0.03 to 5.00 mol / g. <1> ~ <7> 13. The curable composition for imprints according to claim 12, <9> The radical polymerizable group value of the compound A is 100 to 1,500. <1> ~ <8> 13. The curable composition for imprints according to claim 12, <10> The poly(oxyalkylene) group contains an oxyalkylene group represented by the following formula (OA-1): <1> ~ <9> 13. The curable composition for imprints according to claim 12, [ka] In formula (OA-1), R O1 and R O2 each independently represents a hydrogen atom or a methyl group; R O1 and R O2 Both cannot be methyl groups. <11> The content of the poly(oxyalkylene) group in compound C is 0 to 50 mass%. <1> ~ <10> 13. The curable composition for imprints according to claim 12, <12> <1> ~ <11> 2. A cured product obtained by curing the curable composition for imprints according to claim 1. <13> Surface free energy is 10 to 70 mJ / m 2 That is, <12> The cured product according to claim 1. <14> The surface elastic modulus is 0.5 to 3.0 GPa. <12> or <13> The cured product according to claim 1. <15> A member to be applied is selected from the group consisting of a support and a mold. <1> ~ <11> applying the curable composition for imprints according to any one of the above items; a contacting step of contacting a member, which is not selected as the application member from the group consisting of the support and the mold, with the curable composition for imprints as a contact member; a curing step of converting the curable composition for imprints into a cured product; and A peeling step of peeling the mold from the cured product. A method for producing an imprint pattern. <16> the support is a member having an adhesive layer on the surface to which the curable composition for imprints is applied; <15> A method for producing an imprint pattern according to claim 1. <17> <15> or <16> A device manufacturing method comprising the method for manufacturing an imprint pattern according to claim 1. Effect of the Invention

[0009] According to the present invention, there are provided a curable composition for imprints having excellent releasability, a cured product of the curable composition for imprints, a method for producing an imprint pattern using the curable composition for imprints, and a method for producing a device including the method for producing an imprint pattern. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] A representative embodiment of the present invention will be described below. Each component will be described based on this representative embodiment for convenience, but the present invention is not limited to such an embodiment.

[0011] In this specification, a numerical range expressed using the symbol "to" means a range that includes the numerical values ​​before and after "to" as the lower limit and upper limit, respectively. In this specification, the term "process" includes not only an independent process but also a process that cannot be clearly distinguished from other processes, so long as the process can achieve its intended effect. In this specification, when a group (atomic group) is described without specifying whether it is substituted or unsubstituted, it means that it includes both a group (atomic group) that has no substituent and a group (atomic group) that has a substituent. For example, when it is simply described as an "alkyl group", it means that it includes both an alkyl group that has no substituent (unsubstituted alkyl group) and an alkyl group that has a substituent (substituted alkyl group). In this specification, unless otherwise specified, the term "exposure" includes not only drawing using light, but also drawing using particle beams such as electron beams and ion beams. Examples of energy beams used for drawing include the bright line spectrum of a mercury lamp, far ultraviolet light represented by an excimer laser, extreme ultraviolet light (EUV light), and actinic rays such as X-rays, as well as particle beams such as electron beams and ion beams. In this specification, "(meth)acrylate" means both or either of "acrylate" and "methacrylate", "(meth)acrylic" means both or either of "acrylic" and "methacrylic", and "(meth)acryloyl" means both or either of "acryloyl" and "methacryloyl". In this specification, the solid content in a composition means other components excluding the solvent, and the content (concentration) of the solid content in a composition is expressed by the mass percentage of other components excluding the solvent relative to the total mass of the composition, unless otherwise specified. In this specification, unless otherwise specified, the temperature is 23° C., the atmospheric pressure is 101325 Pa (1 atm), and the relative humidity is 50% RH. In this specification, unless otherwise stated, the weight average molecular weight (Mw) and the number average molecular weight (Mn) are shown as polystyrene equivalent values ​​according to gel permeation chromatography (GPC measurement). The weight average molecular weight (Mw) and the number average molecular weight (Mn) can be determined, for example, by using HLC-8220 (manufactured by Tosoh Corporation) and guard columns HZ-L, TSKgel Super HZM-M, TSKgel Super HZ4000, TSKgel Super HZ3000 and TSKgel Super HZ2000 (manufactured by Tosoh Corporation). Unless otherwise stated, the measurements were performed using THF (tetrahydrofuran) as the eluent. Unless otherwise stated, the detection in the GPC measurement was performed using a UV (ultraviolet) wavelength 254 nm detector. In this specification, when the positional relationship of each layer constituting the laminate is described as "upper" or "lower", it is sufficient that there is another layer above or below the reference layer among the multiple layers being noted. In other words, a third layer or element may be interposed between the reference layer and the other layer, and the reference layer does not need to be in contact with the other layer. In addition, unless otherwise specified, the direction in which the layers are stacked on the support is referred to as "upper", or, in the case of a photosensitive layer, the direction from the support to the photosensitive layer is referred to as "upper", and the opposite direction is referred to as "lower". Note that such a vertical direction is set for the convenience of this specification, and in actual embodiments, the "upper" direction in this specification may be different from the vertical upward direction. In this specification, "imprint" refers preferably to pattern transfer having a size of 1 nm to 10 mm, and more preferably to pattern transfer having a size of approximately 10 nm to 100 μm (nanoimprint).

[0012] (Curable composition for imprints) The curable composition for imprints of the present invention contains compound A which is a polymerizable compound having two or more radically polymerizable groups, compound B which is a radical polymerization initiator, and compound C which is at least one kind selected from the group consisting of organopolysiloxanes having only one radically polymerizable group and no poly(oxyalkylene) group, organopolysiloxanes having only one radically polymerizable group and a poly(oxyalkylene) group, and organopolysiloxanes having no radically polymerizable group and a poly(oxyalkylene) group. Hereinafter, among the compounds C, the "organopolysiloxane having only one radically polymerizable group and no poly(oxyalkylene) group" will be referred to as the "compound C-1," the "organopolysiloxane having only one radically polymerizable group and a poly(oxyalkylene) group" will be referred to as the "compound C-2," and the "organopolysiloxane having no radically polymerizable group and a poly(oxyalkylene) group" will be referred to as the "compound C-3."

[0013] The cured product obtained from the curable composition for imprints of the present invention has excellent releasability. The mechanism by which the above effects are obtained is unclear, but is speculated to be as follows.

[0014] The curable composition for imprints of the present invention contains compound C which is at least one selected from the group consisting of organopolysiloxanes having only one radically polymerizable group and no poly(oxyalkylene) group, organopolysiloxanes having only one radically polymerizable group and a poly(oxyalkylene) group, and organopolysiloxanes having no radically polymerizable group and a poly(oxyalkylene) group. When the compound C contains an organopolysiloxane having only one radically polymerizable group (the above-mentioned compound C-1 or C-2), an organopolysiloxane structure derived from the organopolysiloxane structure having only one radically polymerizable group is introduced into the polymer having a high crosslinking density formed by the compound A. This makes it possible to reduce the modulus of elasticity (also referred to as surface modulus of elasticity) near the surface of the imprint pattern, thereby improving releasability from the mold. Furthermore, when the compound C contains an organopolysiloxane having a poly(oxyalkylene) group (the above-mentioned compound C-2 or C-3), the poly(oxyalkylene) group is easily adsorbed to the mold, and therefore the compound C is unevenly distributed on the surface of the imprint pattern. As a result, an organopolysiloxane structure derived from compound C, which has a structure with low surface free energy, is also introduced near the surface of the imprint pattern, thereby reducing the force required to release the imprint pattern from the mold and improving releasability from the mold.

[0015] Furthermore, when compound A is an organopolysiloxane, it is believed that since both compounds A and C have an organopolysiloxane structure, the coating film is less likely to have a non-uniform structure such as a sea-island structure, and the coating film is also excellent in stability. The curable composition for imprints of the present invention will be described in detail below.

[0016] <Compound A> The curable compound for imprints of the present invention contains compound A, which is a polymerizable compound having two or more radically polymerizable groups. In the curable composition for imprints of the present invention, it is preferred that compound A is the component contained in the largest amount among the components other than the solvent contained in the curable composition for imprints.

[0017] [Radically polymerizable group] The radical polymerizable group in compound A is preferably an ethylenically unsaturated bond-containing group, and examples thereof include a (meth)acryloyl group, a (meth)acryloxy group, a (meth)acrylamide group, a vinyl group, a vinyloxy group, an allyl group, a maleimide group, and a group in which a vinyl group is directly bonded to an aromatic ring (e.g., a vinylphenyl group). A (meth)acrylamide group or a (meth)acryloxy group is more preferable, an acrylamide group or an acryloxy group is even more preferable, and an acryloxy group is particularly preferable.

[0018] The radical polymerizable group value of compound A is preferably from 100 to 15,000, more preferably from 200 to 10,000, and further preferably from 300 to 5,000. In this specification, the radical polymerizable group value of a compound is calculated by the following formula. (Radically polymerizable group value)=(number average molecular weight of compound) / (number of polymerizable groups in compound)

[0019] When the radical polymerizable group value is equal to or greater than the lower limit, the elastic modulus during curing is in an appropriate range, and it is considered that the release property is excellent. On the other hand, when the polymerizable group value is equal to or less than the upper limit, the crosslink density of the cured product pattern is in an appropriate range, and it is considered that the resolution of the transfer pattern is excellent.

[0020] [Organopolysiloxane] From the viewpoint of the stability of the coating film, compound A is preferably an organopolysiloxane having two or more radically polymerizable groups. Organopolysiloxane refers to a compound that contains siloxane bonds (-Si-O-Si-O-Si-) as its backbone and has organic groups bonded to the silicon atoms. In the organic group, the atom bonded to the silicon atom is preferably a carbon atom. Atoms or groups other than organic groups (for example, hydrogen atoms, hydroxy groups, hydrolyzable groups, etc.) may be bonded to some of the silicon atoms. The hydrolyzable group is a group that can react with water to become a hydroxy group, and examples of such a group include a halogen atom (such as a chlorine atom), an alkoxy group, an acyl group, and an amino group. The organic group is preferably a hydrocarbon group, more preferably an aromatic hydrocarbon group or a saturated aliphatic hydrocarbon group. The above-mentioned hydrocarbon group, aromatic hydrocarbon group, and saturated aliphatic hydrocarbon group may each further have a substituent. Examples of the substituent include a halogen atom, an alkoxy group, an aryloxy group, and the above-mentioned group containing a radical polymerizable group.

[0021] Compound A is preferably a compound having at least one of a siloxane structure of D units represented by the following formula (S1) and a siloxane structure of T units represented by the following formula (S2). [ka] In formula (S1) or formula (S2), R S1 ~R S3 each independently represents a hydrogen atom or a monovalent substituent, and each * independently represents a bonding site to another structure. R S1 ~R S3 is preferably each independently a monovalent substituent. The monovalent substituent is preferably an aromatic hydrocarbon group (preferably having 6 to 22 carbon atoms, more preferably having 6 to 18 carbon atoms, and even more preferably having 6 to 10 carbon atoms) or an aliphatic hydrocarbon group (preferably having 1 to 24 carbon atoms, more preferably having 1 to 12 carbon atoms, and even more preferably having 1 to 6 carbon atoms), and among these, a cyclic or chain (straight-chain or branched) alkyl group (preferably having 1 to 12 carbon atoms, more preferably having 1 to 6 carbon atoms, and even more preferably having 1 to 3 carbon atoms) or a group containing a polymerizable group is preferable.

[0022] Specific examples of the organopolysiloxane structure, when expressed as a partial structure, include the following formulas (s-1) to (s-9). In the formulas, Q is a group containing the above-mentioned polymerizable group. A compound may have a plurality of these structures, or may have a combination of these structures.

[0023] [ka]

[0024] The organopolysiloxane which is compound A is preferably a reaction product of a silicone resin and a compound having a polymerizable group. The silicone resin is preferably a reactive silicone resin. Examples of the reactive silicone resin include modified silicone resins having the silicone skeleton described above, such as monoamine-modified silicone resins, diamine-modified silicone resins, special amino-modified silicone resins, epoxy-modified silicone resins, alicyclic epoxy-modified silicone resins, carbinol-modified silicone resins, mercapto-modified silicone resins, carboxy-modified silicone resins, hydrogen-modified silicone resins, amino-polyether-modified silicone resins, epoxy-polyether-modified silicone resins, and epoxy-aralkyl-modified silicone resins. The compound having a polymerizable group is preferably a compound having a polymerizable group and a group capable of reacting with an alkoxysilyl group or a silanol group, and more preferably a compound having a polymerizable group and a hydroxy group. In addition, when the modified silicone resin described above is used as the silicone resin, a compound having a polymerizable group and a group that reacts with an amino group, an epoxy group, a mercapto group, a carboxy group, or the like contained in the modified silicone resin may be used as the compound having the polymerizable group. The preferred embodiments of the polymerizable group in the compound having the polymerizable group are the same as the preferred embodiments of the polymerizable group in the above-mentioned polymerizable compound. Among these, the compound having a polymerizable group is preferably a hydroxyalkyl (meth)acrylate, and more preferably 2-hydroxyethyl (meth)acrylate. More specifically, it is preferably a reaction product between a compound having a polymerizable group and a group capable of reacting with an alkoxysilyl group or a silanol group (for example, a hydroxyl group) and a silicone resin having an alkoxysilyl group or a silanol group.

[0025] The weight average molecular weight of the organopolysiloxane which is compound A is preferably from 300 to 10,000, more preferably from 400 to 7,000, and even more preferably from 500 to 5,000.

[0026] The number of radically polymerizable groups in one molecule of the organopolysiloxane that is compound A is preferably 2 or more, more preferably 3 or more, and even more preferably 4 or more. The upper limit is preferably 50 or less, more preferably 40 or less, even more preferably 30 or less, and even more preferably 20 or less.

[0027] The viscosity of the organopolysiloxane of compound A at 23°C is preferably 100 mPa·s or more, more preferably 120 mPa·s or more, and even more preferably 150 mPa·s or more. The upper limit of the viscosity is preferably 2,000 mPa·s or less, more preferably 1,500 mPa·s or less, and even more preferably 1,200 mPa·s or less. In this specification, unless otherwise specified, the viscosity is the value measured using an E-type rotational viscometer RE85L manufactured by Toki Sangyo Co., Ltd., a standard cone rotor (1°34' x R24), and the temperature of the sample cup is adjusted to 23°C. Other details regarding the measurement are in accordance with JIS Z8803:2011. Two samples are prepared for each level, and each is measured three times. The arithmetic average of a total of six measurements is used as the evaluation value.

[0028] [Other high molecular weight polymerizable compounds] Furthermore, compound A may be a high molecular weight polymerizable compound other than the above-mentioned organopolysiloxane. Other examples of high molecular weight polymerizable compounds include compounds containing a cyclic structure (ring-containing compounds) and dendrimer-type compounds.

[0029] The weight average molecular weight of the other high molecular weight polymerizable compound is 800 or more, preferably 1,000 or more, more preferably 1,500 or more, and even more preferably more than 2,000. The upper limit of the weight average molecular weight is not particularly set, but for example, it is preferably 100,000 or less, more preferably 50,000 or less, even more preferably 10,000 or less, even more preferably 8,000 or less, even more preferably 5,000 or less, even more preferably 3,500 or less, and especially more preferably 3,000 or less. By setting the molecular weight to the above lower limit or more, the volatilization of the compound is suppressed, and the properties of the composition and the coating film are stabilized. In addition, good viscosity for maintaining the shape of the coating film can be secured. Furthermore, it is possible to realize good releasability of the film by complementing the effect of suppressing the amount of the release agent to a small amount. By setting the molecular weight to the above upper limit or less, it is easier to secure the low viscosity (fluidity) required for pattern filling, which is preferable.

[0030] -Ring-containing compounds- Examples of the cyclic structure in the compound containing a cyclic structure (ring-containing compound) include an aromatic ring and an alicyclic ring. Examples of the aromatic ring include an aromatic hydrocarbon ring and an aromatic heterocyclic ring. The aromatic hydrocarbon ring preferably has 6 to 22 carbon atoms, more preferably 6 to 18 carbon atoms, and even more preferably 6 to 10 carbon atoms. Specific examples of the aromatic hydrocarbon ring include a benzene ring, a naphthalene ring, an anthracene ring, a phenanthrene ring, a phenalene ring, a fluorene ring, a benzocyclooctene ring, an acenaphthylene ring, a biphenylene ring, an indene ring, an indane ring, a triphenylene ring, a pyrene ring, a chrysene ring, a perylene ring, and a tetrahydronaphthalene ring. Among these, a benzene ring or a naphthalene ring is preferable, and a benzene ring is more preferable. The aromatic ring may have a structure in which a plurality of rings are linked together, and examples of the structure include a biphenyl structure and a diphenylalkane structure (e.g., 2,2-diphenylpropane). (The aromatic hydrocarbon ring defined here is referred to as aCy.) The aromatic heterocycle preferably has 1 to 12 carbon atoms, more preferably 1 to 6, and even more preferably 1 to 5. Specific examples thereof include a thiophene ring, a furan ring, a dibenzofuran ring, a pyrrole ring, an imidazole ring, a benzimidazole ring, a pyrazole ring, a triazole ring, a tetrazole ring, a thiazole ring, a thiadiazole ring, an oxadiazole ring, an oxazole ring, a pyridine ring, a pyrazine ring, a pyrimidine ring, a pyridazine ring, an isoindole ring, an indole ring, an indazole ring, a purine ring, a quinolizine ring, an isoquinoline ring, a quinoline ring, a phthalazine ring, a naphthyridine ring, a quinoxaline ring, a quinazoline ring, a cinnoline ring, a carbazole ring, an acridine ring, a phenazine ring, a phenothiazine ring, a phenoxathiin ring, and a phenoxazine ring. (The aromatic heterocycle defined here is referred to as hCy.) The alicyclic ring preferably has 3 to 22 carbon atoms, more preferably 4 to 18 carbon atoms, and even more preferably 6 to 10 carbon atoms. Specific examples of the aliphatic hydrocarbon ring include a cyclopropane ring, a cyclobutane ring, a cyclobutene ring, a cyclopentane ring, a cyclohexane ring, a cyclohexene ring, a cycloheptane ring, a cyclooctane ring, a dicyclopentadiene ring, a spirodecane ring, a spirononane ring, a tetrahydrodicyclopentadiene ring, an octahydronaphthalene ring, a decahydronaphthalene ring, a hexahydroindane ring, a bornane ring, a norbornane ring, a norbornene ring, an isobornane ring, a tricyclodecane ring, a tetracyclododecane ring, and an adamantane ring. Examples of the aliphatic heterocyclic ring include a pyrrolidine ring, an imidazolidine ring, a piperidine ring, a piperazine ring, a morpholine ring, an oxirane ring, an oxetane ring, an oxolane ring, an oxane ring, and a dioxane ring. (The alicyclic ring defined here is referred to as fCy)

[0031] In the present invention, when the other high molecular weight polymerizable compound is a ring-containing compound, it is preferably a compound containing an aromatic hydrocarbon ring, more preferably a compound having a benzene ring, for example, a compound having a structure represented by the following formula (C-1):

[0032] [ka] In the formula, Ar represents the above aromatic hydrocarbon ring or aromatic heterocycle. L 1 and L 2are each independently a single bond or a linking group. Examples of the linking group include an oxygen atom (oxy group), a carbonyl group, an amino group, an alkylene group (preferably having 1 to 12 carbon atoms, more preferably having 1 to 6 carbon atoms, and even more preferably having 1 to 3 carbon atoms), or a group combining these. Among these, a (poly)alkyleneoxy group is preferable. The (poly)alkyleneoxy group may be one in which the alkyleneoxy group is one or a plurality of repeating alkyleneoxy groups are linked. The order of the alkylene group and the oxy group is not limited. The number of repeating alkyleneoxy groups is preferably 1 to 24, more preferably 1 to 12, and even more preferably 1 to 6. In addition, the (poly)alkyleneoxy group may be interposed by an alkylene group (preferably having 1 to 24 carbon atoms, more preferably having 1 to 12, and even more preferably having 1 to 6 carbon atoms) in the relationship of linkage with the ring Ar or the polymerizable group Q serving as the mother nucleus. Therefore, (poly)alkyleneoxy may be an alkylene group. R 3 is an arbitrary substituent, and examples thereof include an alkyl group (preferably having 1 to 12 carbon atoms, more preferably having 1 to 6 carbon atoms, and more preferably having 1 to 3 carbon atoms), an alkenyl group (preferably having 2 to 12 carbon atoms, more preferably having 2 to 6 carbon atoms, and more preferably having 2 to 3 carbon atoms), an aryl group (preferably having 6 to 22 carbon atoms, more preferably having 6 to 18 carbon atoms, and more preferably having 6 to 10 carbon atoms), an arylalkyl group (preferably having 7 to 23 carbon atoms, more preferably having 7 to 19 carbon atoms, and more preferably having 7 to 11 carbon atoms), a hydroxy group, a carboxy group, an alkoxy group (preferably having 1 to 24 carbon atoms, more preferably having 1 to 12 carbon atoms, and more preferably having 1 to 6 carbon atoms), an acyl group (preferably having 2 to 12 carbon atoms, more preferably having 2 to 6 carbon atoms, and more preferably having 2 to 3 carbon atoms. An alkylcarbonyl group is preferable), and an aryloyl group (preferably having 7 to 23 carbon atoms, more preferably having 7 to 19 carbon atoms, and more preferably having 7 to 11 carbon atoms). L 3 is a single bond or a linking group. The linking group is the same as the above L 1 ,L 2 Examples include: n3 is preferably 3 or less, more preferably 2 or less, even more preferably 1 or less, and particularly preferably 0. Q 1 and Q2 are each independently a polymerizable group, and the above-mentioned examples of polymerizable groups are preferred. In the ring-containing compound, the number of side chains having a polymerizable group increases, which makes it possible to form a strong crosslinked structure during curing, and the resolution tends to improve. From this viewpoint, nq is 1 or more, and preferably 2 or more. The upper limit is preferably 6 or less, more preferably 4 or less, and even more preferably 3 or less. Similarly, from the viewpoint of facilitating the formation of a uniform crosslinked structure, when a group or a substituent containing a polymerizable group is introduced into a cyclic structure, the substituents are preferably arranged in series.

[0033] -Dendrimer type compounds- Other high molecular weight polymerizable compounds may be dendrimer type compounds. Dendrimer means a dendritic polymer having a structure that branches regularly from the center. Dendrimer is composed of a central molecule (trunk) called a core and side chain parts (branches) called dendrons. Although a fan-shaped compound is generally used as a whole, dendrimers in which the dendrons spread out in a semicircular or circular shape may also be used. A group having a polymerizable group can be introduced into the dendron part of this dendrimer (for example, the terminal part away from the core) to make it a polymerizable compound. If a (meth)acryloyl group is used as the polymerizable group to be introduced, a dendrimer type polyfunctional (meth)acrylate can be made. For dendrimer-type compounds, for example, the disclosures in Japanese Patent No. 5512970 can be referred to, and the description of the above publication is incorporated herein by reference.

[0034] -Polymerizable group value- The other high molecular weight polymerizable compound preferably has a polymerizable group value of 130 or more, more preferably 150 or more, even more preferably 160 or more, still more preferably 190 or more, and even more preferably 240 or more. The upper limit of the polymerizable group value is preferably 2,500 or less, more preferably 1,800 or less, even more preferably 1,000 or less, still more preferably 500 or less, even more preferably 350 or less, and may be 300 or less. When the polymerizable group value of the other high molecular weight polymerizable compound is equal to or greater than the lower limit, the elastic modulus during curing is in an appropriate range, and it is considered that the release property is excellent. On the other hand, when the polymerizable group value is equal to or less than the upper limit, the crosslink density of the cured product pattern is in an appropriate range, and it is considered that the resolution of the transfer pattern is excellent.

[0035] The number of polymerizable groups in the other high molecular weight polymerizable compound is 2 or more in one molecule in the case of a ring-containing compound, and the upper limit is preferably 4 or less, and more preferably 3 or less. In the case of a dendrimer type compound, the number in one molecule is preferably 5 or more, more preferably 10 or more, and even more preferably 20 or more. The upper limit is preferably 1,000 or less, more preferably 500 or less, and even more preferably 200 or less.

[0036] The viscosity of the other high molecular weight polymerizable compound at 23° C. is preferably 100 mPa·s or more, more preferably 120 mPa·s or more, and even more preferably 150 mPa·s or more. The upper limit of the viscosity is preferably 2,000 mPa·s or less, more preferably 1,500 mPa·s or less, and even more preferably 1,200 mPa·s or less.

[0037] [Low molecular polymerizable compound] It is also preferable that the composition of the present invention contains, as compound A, a low molecular weight polymerizable compound. The molecular weight of the low molecular weight polymerizable compound is preferably 1,000 or less, and more preferably 100-900. The low molecular weight polymerizable compound is preferably a compound represented by the following formula (2): By using such a compound, adhesion, release force, and stability over time tend to be well-balanced and excellent.

[0038] [ka]

[0039] In formula (2), R 21 is an organic group having a valence of q, and X 1 is a radical polymerizable group, and q is an integer of 2 or more. In formula (2), q is preferably an integer of 2 or more and 7 or less, more preferably an integer of 2 or more and 4 or less, even more preferably 2 or 3, and still more preferably 2. In formula (2), X 1 The preferred embodiments of the radical polymerizable group in are the same as the preferred embodiments of the radical polymerizable group in compound A described above. In formula (2), R 21 R is preferably a divalent to heptavalent organic group, more preferably a divalent to tetravalent organic group, even more preferably a divalent or trivalent organic group, and still more preferably a divalent organic group. 21 is preferably a hydrocarbon group having at least one of a straight-chain, branched, and cyclic structure. The hydrocarbon group preferably has 2 to 20 carbon atoms, and more preferably has 2 to 10 carbon atoms. R 21 When is a divalent organic group, it is preferably an organic group represented by the following formula (1-2). [ka] In the formula, Z 1 and Z 2are each preferably independently a single bond, -O-, -Alk-, or -Alk-O-. Alk represents an alkylene group (preferably having 1 to 12 carbon atoms, more preferably 1 to 6 carbon atoms, and even more preferably 1 to 3 carbon atoms), which may have a substituent within the range in which the effects of the present invention can be obtained.

[0040] R 9 is preferably a single bond or a linking group selected from the following formulae (9-1) to (9-10) or a combination thereof. Of these, a linking group selected from the formulae (9-1) to (9-3), (9-7), and (9-8) is preferred.

[0041] [ka]

[0042] R 101 ~R 117 is an optional substituent. Among them, alkyl groups (preferably having 1 to 12 carbon atoms, more preferably having 1 to 6 carbon atoms, and even more preferably having 1 to 3 carbon atoms), aralkyl groups (preferably having 7 to 21 carbon atoms, more preferably having 7 to 15 carbon atoms, and even more preferably having 7 to 11 carbon atoms), aryl groups (preferably having 6 to 22 carbon atoms, more preferably having 6 to 18 carbon atoms, and even more preferably having 6 to 10 carbon atoms), thienyl groups, furyl groups, (meth)acryloyl groups, (meth)acryloyloxy groups, and (meth)acryloyloxyalkyl groups (the alkyl groups preferably have 1 to 24 carbon atoms, more preferably having 1 to 12 carbon atoms, and even more preferably having 1 to 6 carbon atoms) are preferred. R 101 and R 102 , R 103 and R 104 , R 105 and R 106 , R 107 and R 108 , R 109 and R 110 , R when there are multiple 111 , R when there are multiple 112 , R when there are multiple 113 , R when there are multiple 114 , R when there are multiple 115 , R when there are multiple 116 , R when there are multiple 117may be bonded to each other to form a ring. Ar is an arylene group (preferably having 6 to 22 carbon atoms, more preferably 6 to 18 carbon atoms, and even more preferably 6 to 10 carbon atoms), and specific examples thereof include a phenylene group, a naphthalenediyl group, an anthracenediyl group, a phenanthrenediyl group, and a fluorenediyl group. hCy 1 is a heterocyclic group (preferably having 1 to 12 carbon atoms, more preferably having 1 to 6 carbon atoms, and even more preferably having 2 to 5 carbon atoms), and is more preferably a 5-membered or 6-membered ring. 1 Specific examples of the hetero ring constituting the formula (I) include the above-mentioned aromatic hetero ring hCy, a pyrrolidone ring, a tetrahydrofuran ring, a tetrahydropyran ring, a morpholine ring, and the like, and among these, a thiophene ring, a furan ring, and a dibenzofuran ring are preferred. n and m are natural numbers of 100 or less, preferably 1 to 12, more preferably 1 to 6, and further preferably 1 to 3. p is an integer of 0 or more and up to the maximum number of substitutions possible on each ring. The upper limit is preferably up to half of the maximum number of substitutions possible, more preferably up to 4, and even more preferably up to 2, independently in each case.

[0043] The low molecular weight polymerizable compound is preferably represented by the following formula (2-1). [ka] In formula (2-1), R 9 , Z 1 and Z 2 are R in formula (1-2), 9 , Z 1 and Z 2 The same definition and preferred range are also the same.

[0044] These low molecular weight polymerizable compounds may be contained alone or in combination of two or more kinds.

[0045] The types of atoms constituting the low molecular weight polymerizable compound used in the present invention are not particularly limited, but the compound is preferably composed only of atoms selected from carbon atoms, oxygen atoms, hydrogen atoms, and halogen atoms, and more preferably composed only of atoms selected from carbon atoms, oxygen atoms, and hydrogen atoms.

[0046] Moreover, the low molecular weight polymerizable compound preferably has a polymerizable group value defined above of 150 or more, more preferably 160 or more, even more preferably 190 or more, and still more preferably 240 or more. The upper limit is preferably 2,500 or less, more preferably 1,800 or less, and even more preferably 1,000 or less.

[0047] The low molecular weight polymerizable compound preferably has a cyclic structure, examples of which include an aromatic hydrocarbon ring aCy, an aromatic heterocycle hCy, and an alicyclic ring fCy.

[0048] Other examples of compound A include compounds having two or more radically polymerizable groups, such as the compounds used in the following examples, the compounds described in paragraphs 0017 to 0024 and the examples of JP-A-2014-090133, the compounds described in paragraphs 0024 to 0089 of JP-A-2015-009171, the compounds described in paragraphs 0023 to 0037 of JP-A-2015-070145, and the compounds described in paragraphs 0012 to 0039 of WO 2016 / 152597, but the present invention is not intended to be limited thereto. The curable composition for imprints of the present invention may further contain, among the compounds described in the above publications, a compound having only one radically polymerizable group and not corresponding to compound C. The content of the above compound is preferably from 10 to 70% by mass, more preferably from 20 to 60% by mass, and further preferably from 30 to 50% by mass, based on the total mass of compound A.

[0049] The content of compound A is preferably 30% by mass or more, more preferably 45% by mass or more, even more preferably 50% by mass or more, still more preferably 55% by mass or more, may be 60% by mass or more, or may be 70% by mass or more, based on the total solid content of the curable composition for imprints. The upper limit is preferably less than 99% by mass, more preferably 98% by mass or less, and may be 97% by mass or less.

[0050] The boiling point of the compound A is preferably set and formulated in relation to the polymerizable compound contained in the composition for forming an adhesive layer described later. The boiling point of the polymerizable compound is preferably 500° C. or less, more preferably 450° C. or less, and even more preferably 400° C. or less. The lower limit is preferably 200° C. or more, more preferably 220° C. or more, and even more preferably 240° C. or more.

[0051] <Compound B> The curable composition for imprints contains compound B which is a radical polymerization initiator. The radical polymerization initiator is preferably a thermal radical polymerization initiator or a photoradical polymerization initiator, and a photoradical polymerization initiator is preferred since it can be used in a photoimprint method. The photoradical polymerization initiator may be any compound that generates an active species that polymerizes the above-mentioned polymerizable compound upon irradiation with light. In the present invention, a plurality of types of photoradical polymerization initiators may be used in combination.

[0052] The content of the radical polymerization initiator used in the present invention is, for example, 0.01 to 15 mass %, preferably 0.1 to 12 mass %, and more preferably 0.2 to 7 mass %, based on the total solid content of the curable composition for imprints. When two or more types of radical polymerization initiators are used, the total amount thereof is preferably within the above range. When the content of the photoradical polymerization initiator is 0.01% by mass or more, the sensitivity (fast curing property), resolution, line edge roughness, and coating strength tend to be improved, which is preferable, whereas when the content of the radical polymerization initiator is 15% by mass or less, the light transmittance, colorability, and handling property tend to be improved, which is preferable.

[0053] As the thermal radical polymerization initiator, the components described in JP 2013-036027 A, JP 2014-090133 A, and JP 2013-189537 A can be used. The contents and the like can also be taken into consideration in the descriptions in the above publications.

[0054] The photoradical polymerization initiator used in the present invention may be, for example, a commercially available initiator. For example, those described in paragraph number 0091 of JP-A-2008-105414 may be preferably used. Among these, acetophenone-based compounds, phenyl glyoxylate-based compounds, acylphosphine oxide-based compounds, and oxime ester-based compounds are preferred from the viewpoint of curing sensitivity and absorption characteristics. As the acetophenone compound, preferred are hydroxyacetophenone compounds, dialkoxyacetophenone compounds, and aminoacetophenone compounds. As the hydroxyacetophenone compound, preferred are Irgacure (registered trademark) 2959 (1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propan-1-one, Irgacure (registered trademark) 184 (1-hydroxycyclohexyl phenyl ketone), Irgacure (registered trademark) 500 (1-hydroxycyclohexyl phenyl ketone, benzophenone), and Darocure (registered trademark) 1173 (2-hydroxy-2-methyl-1-phenyl-1-propan-1-one), all of which are available from BASF. A preferred dialkoxyacetophenone compound is Irgacure (registered trademark) 651 (2,2-dimethoxy-1,2-diphenylethan-1-one) available from BASF. Preferred examples of the aminoacetophenone compound include Irgacure (registered trademark) 369 (2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone-1), Irgacure (registered trademark) 379 (EG) (2-dimethylamino-2-(4-methylbenzyl)-1-(4-morpholin-4-ylphenyl)butan-1-one), and Irgacure (registered trademark) 907 (2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone), all of which are available from BASF. Preferred examples of the phenyl glyoxylate compound include Irgacure (registered trademark) 754 and Darocure (registered trademark) MBF available from BASF. Preferred examples of the acylphosphine oxide compound (polymerization initiator having an acylphosphine oxide group in the molecule) available from BASF include Irgacure (registered trademark) 819 (bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide), Irgacure (registered trademark) 1800 (bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl-pentylphosphine oxide), and Lucirin TPO (2,4,6-trimethylbenzoyldiphenylphosphine oxide), and Lucirin TPO-L (2,4,6-trimethylbenzoylphenylethoxyphosphine oxide), available from BASF. Preferred examples of the oxime ester compound available from BASF include Irgacure (registered trademark) OXE01 (1,2-octanedione, 1-[4-(phenylthio)phenyl]-2-(O-benzoyloxime) and Irgacure (registered trademark) OXE02 (ethanone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-, 1-(O-acetyloxime).

[0055] In the present invention, "light" includes not only light with wavelengths in the ultraviolet, near ultraviolet, far ultraviolet, visible, infrared, and other regions, electromagnetic waves, but also radiation. The above radiation includes, for example, microwaves, electron beams, EUV, and X-rays. Laser light such as 248 nm excimer laser, 193 nm excimer laser, and 172 nm excimer laser can also be used. These lights may be monochrome light (single wavelength light) that has passed through an optical filter, or light with multiple different wavelengths (composite light). Exposure can also be multiple exposure, and it is also possible to expose the entire surface after forming a pattern for the purpose of increasing film strength and etching resistance.

[0056] <Compound C> The curable composition for imprints contains at least one compound C selected from the group consisting of organopolysiloxanes having only one radically polymerizable group and no poly(oxyalkylene) group (compound C-1), organopolysiloxanes having only one radically polymerizable group and a poly(oxyalkylene) group (compound C-2), and organopolysiloxanes having no radically polymerizable group and a poly(oxyalkylene) group (compound C-3).

[0057] [Radically polymerizable group] The radical polymerizable group in compound C (i.e., only one radical polymerizable group contained in compound C-1 or compound C-2) is preferably an ethylenically unsaturated bond-containing group, and examples thereof include a (meth)acryloyl group, a (meth)acryloxy group, a (meth)acrylamide group, a vinyl group, a vinyloxy group, an allyl group, a maleimide group, and a group in which a vinyl group is directly bonded to an aromatic ring (e.g., a vinylphenyl group), and the like. A (meth)acrylamide group, a (meth)acryloxy group, or a vinylphenyl group is more preferable, an acrylamide group, an acryloxy group, or a vinylphenyl group is even more preferable, and an acrylamide group is particularly preferable.

[0058] [Poly(oxyalkylene) group] The poly(oxyalkylene) group in compound C (i.e., the poly(oxyalkylene) group contained in compound C-2 or compound C-3) is a group in which two or more oxyalkylene groups are directly bonded, preferably a group in which 5 to 100 oxyalkylene groups are directly bonded, and more preferably a group in which 8 to 50 oxyalkylene groups are directly bonded. The individual oxyalkylene groups contained in the poly(oxyalkylene) group may be the same or different in structure. Furthermore, when the poly(oxyalkylene) group contains two or more types of oxyalkylene groups having different structures, for example, the poly(oxyalkylene) group may be a group in which two or more types of oxyalkylene groups having different structures are randomly bonded, or may contain a block of oxyalkylene groups of one structure and a block of oxyalkylene groups of another structure, and the arrangement of the oxyalkylene groups is not particularly limited. The alkylene group in the polyoxyalkylene group preferably has 2 to 10 carbon atoms, more preferably 2 to 4 carbon atoms, and even more preferably 2 or 3 carbon atoms.

[0059] The poly(oxyalkylene) group preferably contains an oxyalkylene group represented by the following formula (OA-1), and more preferably is a group consisting of an oxyalkylene group represented by the following formula (OA-1). [ka] In formula (OA-1), R O1 and R O2 each independently represents a hydrogen atom or a methyl group; R O1 and R O2 Both cannot be methyl groups.

[0060] The poly(oxyalkylene) group is preferably a poly(ethyleneoxy) group, a poly(ethyleneoxy-ran-propyleneoxy) group, or a poly(ethyleneoxy-block-propyleneoxy) group. Poly(A-ran-B) means that A and B are bonded randomly, and poly(A-block-B) means that a block formed by A and a block formed by B are bonded.

[0061] When compound C contains a poly(oxyalkylene) group, the content (i.e., the content of poly(oxyalkylene) group in compound C-2 or compound C-3) is preferably 50% by mass or less, more preferably 40% by mass or less, and even more preferably 30% by mass or less, based on the total mass of the composition. The lower limit of the content is not particularly limited, but can be, for example, 1% by mass or more.

[0062] [Repeating unit represented by formula (S-1)] Compound C preferably contains a repeating unit represented by the following formula (S-1). [ka] In formula (S-1), each R independently represents a hydrocarbon group.

[0063] In formula (S-1), each R is preferably an aromatic hydrocarbon group or an alkyl group, more preferably a phenyl group or a methyl group, and further preferably a methyl group.

[0064] The content of the repeating unit represented by formula (S-1) in compound C-1 is preferably from 50 to 95% by mass, more preferably from 60 to 90% by mass, and further preferably from 70 to 85% by mass. The content of the repeating unit represented by formula (S-1) in compound C-2 is preferably from 5 to 80 mass %, more preferably from 8 to 70 mass %, and further preferably from 10 to 50 mass %. The content of the repeating unit represented by formula (S-1) in compound C-3 is preferably from 5 to 80 mass %, more preferably from 8 to 70 mass %, and further preferably from 10 to 50 mass %.

[0065] Compound C may contain at least one structure selected from the group consisting of a structure represented by the following formula (S2) and a structure represented by the following formula (S3). Furthermore, an embodiment in which compound C does not contain either a structure represented by the following formula (S2) or a structure represented by the following formula (S3) is also one of the preferred embodiments of the present invention. [ka] In formula (S2) or formula (S3), R S3 represents a hydrogen atom or a monovalent substituent, and each * independently represents a bonding site to another structure. R S3 is preferably a monovalent substituent. The monovalent substituent is preferably an aromatic hydrocarbon group (preferably having 6 to 22 carbon atoms, more preferably having 6 to 18 carbon atoms, and even more preferably having 6 to 10 carbon atoms) or an aliphatic hydrocarbon group (preferably having 1 to 24 carbon atoms, more preferably having 1 to 12 carbon atoms, and even more preferably having 1 to 6 carbon atoms), and among these, a cyclic or chain (straight-chain or branched) alkyl group (preferably having 1 to 12 carbon atoms, more preferably having 1 to 6 carbon atoms, and even more preferably having 1 to 3 carbon atoms) or a group containing a polymerizable group is preferable.

[0066] [Structural unit represented by formula (S-2)] Compound C-2 or compound C-3 preferably contains a structural unit represented by the following formula (S-2). Compound C-2 or compound C-3 may contain only one constitutional unit represented by the following formula (S-2), or may contain two or more constitutional units. [ka] In formula (S-2), R represents a hydrocarbon group; S1 represents a group having a poly(oxyalkylene) group.

[0067] In formula (S-2), the preferred embodiments of R are the same as those in formula (S-1). In formula (S-2), R S1The preferred embodiments of the poly(oxyalkylene) group in the above-mentioned compound C are the same as those in the above-mentioned compound C. In formula (S-2), R S1 is preferably a group represented by the following formula (RS-1). [ka] In formula (RS-1), L S1 represents a single bond or a divalent linking group, R OA represents a poly(oxyalkylene) group, R S2 represents a hydrogen atom or a monovalent organic group, and * represents a bonding site with the silicon atom in formula (S-2). In formula (RS-1), L S1 is preferably a single bond, a hydrocarbon group, or a group represented by a bond between one or more hydrocarbon groups and at least one compound selected from the group consisting of -O-, -CO-, -S-, -SO2-, or -NHCO-, and is preferably a single bond, a hydrocarbon group, or a group represented by a bond between a hydrocarbon group and -O-. L S1 The hydrocarbon group in is preferably a hydrocarbon group having 2 to 20 carbon atoms, more preferably a hydrocarbon group having 2 to 10 carbon atoms, and further preferably a hydrocarbon group having 2 to 4 carbon atoms. Also, L S1 The hydrocarbon group in may be either an aliphatic hydrocarbon group or an aromatic hydrocarbon group, but is preferably an alkylene group, an aromatic hydrocarbon group, or a group represented by a combination thereof, and more preferably an alkylene group. In formula (RS-1), R OA The preferred embodiments of the poly(oxyalkylene) group in the above are the same as the preferred embodiments of the poly(oxyalkylene) group in the above compound C. In compound C-2, in formula (RS-1), R S2 is preferably a hydrogen atom, a hydrocarbon group, the above-mentioned radically polymerizable group, or a group represented by a combination of a hydrocarbon group and the above-mentioned radically polymerizable group. In compound C-3, R S2is preferably a hydrogen atom or a hydrocarbon group. R S2 The hydrocarbon group in is preferably a hydrocarbon group having 2 to 20 carbon atoms, more preferably a hydrocarbon group having 2 to 10 carbon atoms, and further preferably a hydrocarbon group having 2 to 4 carbon atoms. Also, L S1 The hydrocarbon group in may be either an aliphatic hydrocarbon group or an aromatic hydrocarbon group, but is more preferably an alkyl group, an aromatic hydrocarbon group, or a group represented by a combination thereof.

[0068] Specific examples of the structural unit represented by formula (S-2) are shown below, but the present invention is not limited thereto. In the structural formulas below, the subscripts in parentheses indicate the number of repetitions. In this specification, unless otherwise specified, (C x H 2x O) n (C y H 2y O) m The description of is n (C x H 2x O) block and m (C y H 2y O) block. [ka]

[0069] The content of the constitutional unit represented by formula (S-2) in compound C-2 is preferably from 5 to 80 mass %, more preferably from 8 to 70 mass %, and further preferably from 10 to 50 mass %. The content of the constitutional unit represented by formula (S-2) in compound C-3 is preferably from 5 to 80 mass %, more preferably from 8 to 70 mass %, and even more preferably from 10 to 50 mass %.

[0070] [Structure represented by formula (S-3)] Moreover, compound C-2 or compound C-3 preferably contains a structure represented by the following formula (S-3). [ka] In formula (S-3), each R independently represents a hydrocarbon group; S3 represents a group having a poly(oxyalkylene) group, and * represents a bonding site with another structure.

[0071] In formula (S-3), the preferred embodiments of R are the same as those of R in formula (S-1). In formula (S-3), R S3 The preferred embodiments of the poly(oxyalkylene) group in the above-mentioned compound C are the same as those in the above-mentioned compound C. In formula (S-3), R S3 is preferably a group represented by the above formula (RS-1). In formula (S-3), * is preferably a bonding site to an oxygen atom in the repeating unit represented by formula (S-1) or an oxygen atom in the constitutional unit represented by formula (S-2), and more preferably a bonding site to an oxygen atom in the repeating unit represented by formula (S-1).

[0072] Specific examples of the structure represented by formula (S-3) are shown below, but the present invention is not limited thereto. In the following structural formula, * is the same as * in formula (S-3), and the subscript in parentheses indicates the number of repetitions. [ka]

[0073] The content of the structure represented by formula (S-3) in compound C-2 is preferably from 5 to 80 mass %, more preferably from 8 to 70 mass %, and further preferably from 10 to 50 mass %. The content of the structure represented by formula (S-3) in compound C-3 is preferably from 5 to 80 mass %, more preferably from 8 to 70 mass %, and further preferably from 10 to 50 mass %.

[0074] [Structural unit represented by formula (S-4)] Compound C-1 or compound C-2 may contain only one constitutional unit represented by the following formula (S-4). [ka] In formula (S-4), R represents a hydrocarbon group; S4 represents a group having a radical polymerizable group.

[0075] In formula (S-4), the preferred embodiments of R are the same as those of R in formula (S-1). In formula (S-4), R S4 The preferred embodiments of the radical polymerizable group in the above-mentioned compound C are the same as those in the above-mentioned compound C. In formula (S-4), R S4 is preferably a group represented by the following formula (RS-4). [ka] In formula (RS-4), L S2 represents a single bond or a divalent linking group, R S5 represents a radically polymerizable group, and * represents a bonding site with the silicon atom in formula (S-4). In formula (RS-4), L S2 is preferably a linking group consisting of an organic group, and more preferably a hydrocarbon group. L S2 Examples of the hydrocarbon group in include an alkylene group (preferably having 1 to 24 carbon atoms, more preferably having 2 to 12 carbon atoms, and even more preferably having 2 to 6 carbon atoms), an alkenylene group (preferably having 2 to 24 carbon atoms, more preferably having 2 to 12 carbon atoms, and even more preferably having 2 to 6 carbon atoms), and an aromatic hydrocarbon group (preferably having 6 to 22 carbon atoms, more preferably having 6 to 18 carbon atoms, and even more preferably having 6 to 10 carbon atoms). S2 An embodiment in which contains the above-mentioned poly(oxyalkylene) group is also one of the preferred embodiments of the present invention. In compound C-1, R S5 does not contain the poly(oxyalkylene) groups described above. In formula (RS-4), R S5The preferred embodiments of the radical polymerizable group in the above-mentioned compound C are the same as those in the above-mentioned compound C.

[0076] Specific examples of the constitutional unit represented by formula (S-4) are shown below, but the present invention is not limited thereto. In the structural formula below, the subscripts in parentheses indicate the number of repetitions. [ka]

[0077] [Structure represented by formula (S-5)] Compound C-1 or compound C-2 may contain only one structure represented by the following formula (S-5). [ka] In formula (S-5), each R independently represents a hydrocarbon group; S6 represents a group having a radically polymerizable group, and * represents a bonding site with another structure.

[0078] In formula (S-5), the preferred embodiments of R are the same as those of R in formula (S-1). In formula (S-5), R S6 The preferred embodiments of the radical polymerizable group in the above-mentioned compound C are the same as those in the above-mentioned compound C. In formula (S-5), R S6 is preferably a group represented by the above formula (RS-4). In formula (S-5), * is preferably a bonding site to an oxygen atom in the repeating unit represented by formula (S-1) or an oxygen atom in the constitutional unit represented by formula (S-2), and more preferably a bonding site to an oxygen atom in the repeating unit represented by formula (S-1).

[0079] Specific examples of the structure represented by formula (S-5) are shown below, but the present invention is not limited thereto. In the following structural formula, * is the same as * in formula (S-5), and the subscript in parentheses indicates the number of repetitions. [ka]

[0080] [Specific examples] Specific examples of compound C include G-1 to G-16 described in the Examples below. Among the above G-1 to G-16, G-1 to G-2 and G-5 to G-6 correspond to the compound C-1. G-3 to G-4 and G-11 to G-12 correspond to compound C-2. G-7 to G-10 and G-13 to G-16 correspond to compound C-3.

[0081] [Physical Properties] The difference in SP (solubility parameter) between compound A and compound C is 5 (MPa). 1 / 2 It is preferable that the temperature is 3 (MPa) or less. 1 / 2 More preferably, it is 1 (MPa) or less. 1 / 2 It is more preferable that: In the present invention, the SP value is a value determined by the Okitsu method. The Okitsu method is one of the conventionally well-known methods for calculating the sp value, and is described in detail, for example, in the Journal of the Adhesion Society of Japan, Vol. 29, No. 6 (1993), pp. 249-259.

[0082] [Molecular weight] The weight average molecular weight of compound C is preferably from 500 to 15,000, more preferably from 700 to 8,000, and further preferably from 900 to 5,000.

[0083] [Content] The content of compound C used in the present invention is, for example, 0.01 to 15 mass %, preferably 0.1 to 12 mass %, and more preferably 0.2 to 7 mass %, based on the total solid content of the curable composition for imprints. When two or more types of compound C are used, the total amount thereof is preferably within the above range. From the viewpoint of releasability, the ratio of the total mass of compound C to the total mass of compound A contained in the composition (total mass of compound C / total mass of compound A×100) is preferably 0.2 to 20 mass%, more preferably 0.5 to 15 mass%, and even more preferably 1.0 to 10 mass%.

[0084] [Release Agent] The curable composition for imprints of the present invention may further contain a release agent. The content of the release agent is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, even more preferably 0.5% by mass or more, and particularly preferably 0.6% by mass or more, based on the total solid content of the composition. The upper limit is preferably less than 1.0% by mass, more preferably 0.9% by mass or less, and even more preferably 0.85% by mass or less. By setting the content of the release agent to the above lower limit or more, the releasability is improved, and peeling of the cured film and damage to the mold during release can be prevented. On the other hand, by setting the content to the above upper limit or less, an excessive decrease in pattern strength during curing due to the influence of the release agent is not caused, and good resolution can be achieved. The release agent may be used alone or in combination with a plurality of types. When a plurality of types are used, the total amount of the release agents falls within the above range. The type of release agent is not particularly limited, but preferably has a function of segregating at the interface with the mold and effectively promoting release from the mold. In the present invention, it is preferable that the release agent is substantially free of fluorine atoms and silicon atoms. Substantially free means that the total amount of fluorine atoms and silicon atoms is 1 mass % or less of the release agent, preferably 0.5 mass % or less, more preferably 0.1 mass % or less, and even more preferably 0.01 mass % or less. By using a release agent that is substantially free of fluorine atoms and silicon atoms, it is preferable from the viewpoint of making the curable composition for imprints excellent in processing resistance against etching and the like while realizing high releasability of the film. Specifically, the release agent used in the present invention is preferably a surfactant. Alternatively, it is preferably an alcohol compound having at least one hydroxy group at the end, or a compound having a (poly)alkylene glycol structure in which the hydroxy group is etherified ((poly)alkylene glycol compound). The surfactant and (poly)alkylene glycol compound are preferably non-polymerizable compounds having no polymerizable group. The (poly)alkylene glycol may mean one having one alkylene glycol structure or one having multiple repeating alkylene glycol structures linked together.

[0085] -Surfactants- As the surfactant that can be used as the release agent in the present invention, a nonionic surfactant is preferred. A nonionic surfactant is a compound having at least one hydrophobic part and at least one nonionic hydrophilic part. The hydrophobic part and the hydrophilic part may be at the terminal or inside of the molecule. The hydrophobic part is composed of, for example, a hydrocarbon group, and the number of carbon atoms in the hydrophobic part is preferably 1 to 25, more preferably 2 to 15, further preferably 4 to 10, and even more preferably 5 to 8. The nonionic hydrophilic part preferably has at least one group selected from the group consisting of an alcoholic hydroxy group, a phenolic hydroxy group, an ether group (preferably a (poly)alkyleneoxy group, a cyclic ether group), an amide group, an imide group, a ureido group, a urethane group, a cyano group, a sulfonamide group, a lactone group, a lactam group, and a cyclocarbonate group. Among them, a compound having an alcoholic hydroxy group or an ether group (preferably a (poly)alkyleneoxy group, a cyclic ether group) is more preferable.

[0086] -Alcohol compounds, (poly)alkylene glycol compounds- As described above, preferred releasing agents for use in the curable composition for imprints of the present invention include alcohol compounds having at least one hydroxy group at an end, or (poly)alkylene glycol compounds in which a hydroxy group has been etherified.

[0087] Specifically, the (poly)alkylene glycol compound preferably has an alkyleneoxy group or a polyalkyleneoxy group, and more preferably has a (poly)alkyleneoxy group containing an alkylene group having 1 to 6 carbon atoms. Specifically, it is preferable to have a (poly)ethyleneoxy group, a (poly)propyleneoxy group, a (poly)butyleneoxy group, or a mixed structure thereof, more preferably a (poly)ethyleneoxy group, a (poly)propyleneoxy group, or a mixed structure thereof, and even more preferably a (poly)propyleneoxy group. The (poly)alkylene glycol compound may be substantially composed of only (poly)alkyleneoxy groups, except for the terminal substituent. Here, "substantially" means that the components other than the (poly)alkyleneoxy group are 5% by mass or less of the total, and preferably 1% by mass or less. In particular, it is particularly preferable to include a compound substantially composed of only (poly)propyleneoxy groups as the (poly)alkylene glycol compound.

[0088] In the (poly)alkylene glycol compound, the number of repeating alkyleneoxy groups is preferably 3-100, more preferably 4-50, even more preferably 5-30, and even more preferably 6-20.

[0089] As long as the terminal hydroxyl group of the (poly)alkylene glycol compound is etherified, the remaining terminal may be a hydroxyl group, or the hydrogen atom of the terminal hydroxyl group may be substituted. The group with which the hydrogen atom of the terminal hydroxyl group may be substituted is preferably an alkyl group (i.e., a (poly)alkylene glycol alkyl ether) or an acyl group (i.e., a (poly)alkylene glycol ester). Compounds having multiple (preferably 2 or 3) (poly)alkylene glycol chains via a linking group can also be preferably used.

[0090] Preferred specific examples of the (poly)alkylene glycol compound include polyethylene glycol, polypropylene glycol (e.g., manufactured by Wako Pure Chemical Industries, Ltd.), their mono- or dimethyl ethers, mono- or dibutyl ethers, mono- or dioctyl ethers, mono- or dicetyl ethers, monostearate esters, monooleate esters, polyoxyethylene glyceryl ethers, polyoxypropylene glyceryl ethers, polyoxyethylene lauryl ethers, and trimethyl ethers thereof.

[0091] The (poly)alkylene glycol compound is preferably a compound represented by the following formula (P1) or (P2). [ka] R in the formula P1 R is an alkylene group (preferably having 1 to 12 carbon atoms, more preferably having 1 to 6 carbon atoms, and even more preferably having 1 to 3 carbon atoms) which may be chain-like or cyclic, and may be straight-chain or branched. P2 , R P3 is a hydrogen atom or an alkyl group (preferably having 1 to 36 carbon atoms, more preferably 2 to 24 carbon atoms, and even more preferably 3 to 12 carbon atoms), which may be chain-like or cyclic, straight-chain or branched. p is preferably an integer of 1 to 24, and more preferably an integer of 2 to 12. R P4 is a linking group having a valence of q, and is preferably a linking group made of an organic group, and is preferably a linking group made of a hydrocarbon. Specific examples of the linking group made of a hydrocarbon include a linking group having an alkane structure (preferably having 1 to 24 carbon atoms, more preferably having 2 to 12 carbon atoms, and even more preferably having 2 to 6 carbon atoms), a linking group having an alkene structure (preferably having 2 to 24 carbon atoms, more preferably having 2 to 12 carbon atoms, and even more preferably having 2 to 6 carbon atoms), and a linking group having an aryl structure (preferably having 6 to 22 carbon atoms, more preferably having 6 to 18 carbon atoms, and even more preferably having 6 to 10 carbon atoms). q is preferably an integer of 2 to 8, more preferably an integer of 2 to 6, and further preferably an integer of 2 to 4.

[0092] The weight average molecular weight of the alcohol compound or (poly)alkylene glycol compound used as a release agent is preferably 150-6,000, more preferably 200-3,000, further preferably 250-2,000, and even more preferably 300-1,200. In addition, examples of commercially available (poly)alkylene glycol compounds that can be used in the present invention include Olfine E1010 (manufactured by Nissin Chemical Industry Co., Ltd.) and Brij35 (manufactured by Kishida Chemical Industry Co., Ltd.).

[0093] <Solvent> The curable composition for imprints of the present invention may contain a solvent. When a solvent-containing curable composition for imprints is used, the solvent can be removed, for example, by drying to obtain a curable film. In the present invention, when the curable composition for imprints contains a solvent, the content of the solvent is preferably 90.0 to 99.0 mass %, more preferably 92.0 to 99.0 mass %, and further preferably 95.0 to 99.0 mass %, based on the total mass of the curable composition for imprints.

[0094] The solvent contained in the curable composition for imprints is preferably a solvent having a boiling point of 80 to 200° C. at 1 atmospheric pressure. The type of solvent is not particularly limited, but is preferably a solvent having one or more of an ester structure, a ketone structure, a hydroxy group, and an ether structure, and examples of the solvent include propylene glycol monomethyl ether acetate, cyclohexanone, 2-heptanone, gamma-butyrolactone, propylene glycol monomethyl ether, and ethyl lactate. These solvents may be used alone or in combination. Among these, a solvent containing propylene glycol monomethyl ether acetate is most preferable from the viewpoint of coating uniformity.

[0095] <Other additives> The curable composition for imprints of the present invention may contain additives other than the above-mentioned Compounds A to C, release agent, and solvent, such as a surfactant, a sensitizer, an antioxidant, and a polymerization inhibitor. Specific examples of other additives contained in the curable composition for imprints that can be used in the present invention include additives contained in the compositions described in JP-A-2013-036027, JP-A-2014-090133, and JP-A-2013-189537, the contents of which are incorporated herein by reference. In addition, the descriptions in the above publications can be referred to for the preparation of the curable composition for imprints and the method for producing a pattern, the contents of which are incorporated herein by reference by reference.

[0096] <Physical properties, etc.> The molar amount of the radically polymerizable group relative to the total solid content of the curable composition for imprints is preferably from 0.03 to 5.00 mol / g, more preferably from 0.05 to 4.50 mol / g, and further preferably from 0.08 to 4.00 mol / g.

[0097] The viscosity of a composition obtained by removing the solvent from the curable composition for imprints (i.e., a composition prepared by mixing the components (solids) other than the solvent in the curable composition for imprints) is preferably 20.0 mPa·s or less, more preferably 15.0 mPa·s or less, even more preferably 11.0 mPa·s or less, and still more preferably 9.0 mPa·s or less. The lower limit of the viscosity is not particularly limited, but can be, for example, 5.0 mPa·s or more. The viscosity can be measured by a known method, for example, it is measured according to the following method.

[0098] Viscosity is measured using a Toki Sangyo Co., Ltd. E-type rotational viscometer RE85L with a standard cone rotor (1°34' x R24) and the sample cup is adjusted to a temperature of 23°C. The unit is mPa·s. Other details regarding the measurement are in accordance with JIS Z8803:2011. Two samples are prepared for each level, and each is measured three times. The arithmetic average of a total of six measurements is used as the evaluation value.

[0099] The surface tension (γResist) of the composition obtained by removing the solvent from the curable composition for imprints is preferably 28.0 mN / m or more, more preferably 30.0 mN / m or more, and may be 32.0 mN / m or more. By using a composition with high surface tension, the capillary force increases, and the composition can be quickly filled into the mold pattern. The upper limit of the surface tension is not particularly limited, but from the viewpoint of the relationship with the adhesive layer and imparting inkjet suitability, it is preferably 40.0 mN / m or less, more preferably 38.0 mN / m or less, and may be 36.0 mN / m or less. The surface tension of the curable composition for imprints from which the solvent has been removed is measured at 23° C. using a surface tensiometer SURFACE TENS-IOMETER CBVP-A3 manufactured by Kyowa Interface Science Co., Ltd., and a glass plate.

[0100] The Onishi parameter of a composition obtained by removing the solvent from the curable composition for imprints is preferably not more than 5.0, more preferably not more than 4.0, and even more preferably not more than 3.7. The lower limit of the Onishi parameter of the composition obtained by removing the solvent from the curable composition for imprints is not particularly limited, but may be, for example, not less than 1.0, or even not less than 2.0. The Ohnishi parameter can be determined for the solid content of the curable composition for imprints by substituting the numbers of carbon atoms, hydrogen atoms, and oxygen atoms of all the constituent components into the following formula. Onishi parameter = sum of the number of carbon atoms, hydrogen atoms, and oxygen atoms / (number of carbon atoms - number of oxygen atoms)

[0101] <Storage container> A conventionally known container can be used as the container for the curable composition for imprints of the present invention. In addition, it is also preferable to use a multi-layer bottle whose inner wall is made of six types of six-layer resins or a bottle with a seven-layer structure made of six types of resins, in order to prevent impurities from being mixed into the raw materials or the composition. Examples of such containers include the containers described in JP2015-123351A.

[0102] (Method of producing cured product and imprint pattern) The cured product of the present invention is a cured product obtained by curing the curable composition for imprints of the present invention. The cured product of the present invention is preferably a patterned cured product (imprint pattern).

[0103] The surface free energy of the cured product of the present invention is 10 to 70 mJ / m 2 is preferably 15 to 60 mJ / m 2 More preferably, it is 20 to 50 mJ / m 2 It is more preferable that: The surface free energy γa is a value obtained by the following formula (1). Formula (1): γa = γa d +γa p In formula (1), γa d and γ p respectively represent the dispersive component and the polar component of the surface free energy of the adhesive film surface derived based on the Kaelbel-Uy theory.

[0104] The surface free energy is measured by first dropping a plurality of solvents, each of which has a known dispersive component and polar component of the surface free energy, onto a cured product formed on a substrate such as a glass plate, and measuring the contact angle of each solvent. Next, the measured contact angles are applied to the following formula (1-2) to obtain the γa d and γ p γa can be obtained by solving the simultaneous equations for Formula (1-2): γL(1-cosθ)=2√(γad γL d )+2√(γa p γL p ) In formula (1-2), θ represents the contact angle of the solvent on the adhesive film, γL is the surface free energy of the solvent (mJ / m 2 ), γL d represents the dispersive component of the surface free energy of the solvent, γL p represents the polar component of the surface free energy of the solvent, γL=γL d +γL p Meet the following.

[0105] The contact angle was measured using, for example, a fully automatic contact angle meter DMo-901 (manufactured by Kyowa Interface Science Co., Ltd.). In the measurement of surface free energy, the atmosphere is, for example, atmospheric pressure, and the temperature is For example, 23°C. In applying the Kaelbel-Uy theory, the surface free energy Solvents with known dispersive and polar components of energy are water, diiodomethane, and formaldehyde. amide, oleic acid and n-hexadecane can be used. To calculate the surface free energy of a solid surface based on the y-theory, at least two solvents are required. In the present invention, the combination of water and diiodomethane is preferentially used. And, if for some reason it is impossible or practical to measure the contact angle, If any of the solvents are not available, the solvents are changed to solvents that are practically measurable. The solvents employed by the present inventors are selected from the group consisting of formamide, oleic acid and n-hexadecane. The order of priority of these solvents is formamide > oleamide. For more details on the Kaelbel-Uy theory, see e.g. , Journal of the Adhesion Society of Japan Vol. 52, No. 6 (2016) pp. 171-175 , the contents of which are incorporated herein.

[0106] The surface elastic modulus of the cured product of the present invention is preferably from 0.5 to 3.0 GPa, more preferably from 0.6 to 2.5 GPa, and even more preferably from 0.7 to 2.0 GPa. The surface elastic modulus is measured by an atomic force microscope (AFM). A method for producing an imprint pattern will now be described.

[0107] <Method of manufacturing imprint pattern> The method for producing an imprint pattern of the present invention includes the steps of: applying the curable composition for imprints of the present invention to a member to which the composition is to be applied, the member being selected from the group consisting of a support and a mold; a contacting step of contacting a member, which is not selected as the application member from the group consisting of the support and the mold, with the curable composition for imprints as a contact member; a curing step of converting the curable composition for imprints into a cured product; and The method includes a peeling step of peeling the mold from the cured product.

[0108] [Applicable process] The method for producing an imprint pattern of the present invention includes an applying step of applying the curable composition for imprints of the present invention to a member to which the composition is to be applied, the member being selected from the group consisting of a support and a mold. In the applying step, one member selected from the group consisting of a support and a mold is selected as a member to which the composition is applied, and the curable composition for imprints of the present invention is applied onto the selected member to which the composition is applied. One of the support body and the mold is selected as the applied member, and the other is selected as the contact member. That is, in the application step, the curable composition for imprints of the present invention may be applied to a support and then brought into contact with a mold, or may be applied to a mold and then brought into contact with a support (which may have an adhesion layer or the like described below).

[0109] -Support- As for the support, the description in paragraph 0103 of JP 2010-109092 A (corresponding US application is US Patent Application Publication No. 2011 / 0199592) can be referred to, and the contents thereof are incorporated herein. Specific examples include silicon substrates, glass substrates, sapphire substrates, silicon carbide substrates, gallium nitride substrates, metal aluminum substrates, amorphous aluminum oxide substrates, polycrystalline aluminum oxide substrates, GaAsP, GaP, AlGaAs, InGaN, GaN, AlGaN, ZnSe, AlGaInP, or substrates made of ZnO. Specific examples of the material of the glass substrate include aluminosilicate glass, aluminoborosilicate glass, and barium borosilicate glass. In the present invention, the substrate is preferably a silicon substrate.

[0110] The support is preferably a member having an adhesive layer on the surface to which the curable composition for imprints is applied. The adhesion layer is preferably an adhesion layer formed by applying a composition for forming an adhesion layer, which will be described later, to a support. The support may further include a liquid film, which will be described later, on the surface of the adhesive layer opposite to the surface in contact with the support. The liquid film is preferably a liquid film formed by applying a liquid film-forming composition, which will be described later, onto the adhesive layer.

[0111] Examples of the adhesion layer that can be used include those described in paragraphs 0017 to 0068 of JP 2014-024322 A and paragraphs 0016 to 0044 of JP 2013-093552 A, adhesion layers described in JP 2014-093385 A, and adhesion layers described in JP 2013-202982 A, the contents of which are incorporated herein by reference.

[0112] -Mold- In the present invention, the mold is not particularly limited. Regarding the mold, the description in paragraphs 0105 to 0109 of JP 2010-109092 A (corresponding US application is US Patent Application Publication No. 2011 / 0199592) can be referred to, and the contents thereof are incorporated herein. As the mold used in the present invention, a quartz mold is preferable. The pattern (line width) of the mold used in the present invention is preferably 50 nm or less in size. The above mold pattern can be formed according to the desired processing accuracy by, for example, photolithography or electron beam drawing, but in the present invention, the mold pattern manufacturing method is not particularly limited. Moreover, the mold on which the imprint pattern is formed is preferably one including any one of a line, hole, and pillar shape. Among these, a mold on which an imprint pattern including any one of lines, holes, and pillars with a size of 100 nm or less is formed is preferable.

[0113] -How to apply- The method for applying the curable composition for imprints of the present invention to a member to which the composition is applied is not particularly limited, and any commonly known application method can be used, such as dip coating, air knife coating, curtain coating, wire bar coating, gravure coating, extrusion coating, spin coating, slit scanning, and inkjet coating. Among these, the inkjet method and the spin coating method are preferable. The curable composition for imprints may also be applied by multiple applications. In the method of disposing droplets by the inkjet method, the volume of the droplets is preferably about 1 to 20 pL, and the droplets are preferably disposed on the support surface with intervals between them. The interval between droplets may be appropriately set according to the volume of the droplets, but an interval of 10 to 1000 μm is preferable. In the case of the inkjet method, the interval between droplets is set to the interval between the nozzles of the inkjet. The inkjet method has an advantage that there is little loss of the curable composition for imprints. Specific examples of methods for applying the curable composition for imprints by the inkjet system include the methods described in JP2015-179807A and WO2016 / 152597A, and the like. The methods described in these documents can also be suitably used in the present invention. On the other hand, the spin coating method has the advantage that the coating process is highly stable and the range of usable materials is wider. Specific examples of methods for applying the curable composition for imprints by spin coating include the methods described in JP-A-2013-095833 and JP-A-2015-071741, and the methods described in these documents can also be suitably used in the present invention.

[0114] -Drying process- The method for producing an imprint pattern of the present invention may further include a drying step of drying the curable composition for imprints of the present invention applied in the applying step. In particular, when a solvent-containing composition is used as the curable composition for imprints of the present invention, the method for producing an imprint pattern of the present invention preferably includes a drying step. In the drying step, at least a part of the solvent contained in the applied curable composition for imprints of the present invention is removed. The drying method is not particularly limited, and drying by heating, drying by blowing air, etc. can be used without any particular limitation, but drying by heating is preferred. The heating means is not particularly limited, and a known hot plate, oven, infrared heater, etc. can be used. In the present invention, the layer formed from the curable composition for imprints after the applying step and the drying step, which is performed as necessary, but before the contacting step, is also referred to as a "curable film".

[0115] [Contact process] The method for producing an imprint pattern of the present invention includes a contacting step of contacting a member not selected as the application member from the group consisting of the support and the mold with the curable composition for imprints (curable film) as a contact member. When a support is selected as the member to be applied in the above-mentioned applying step, in the contacting step, a mold, which is a contact member, is brought into contact with the surface of the support to which the curable composition for imprints of the present invention has been applied (the surface on which the curable film has been formed). When a mold is selected as the member to be treated in the above-mentioned applying step, in the contacting step, a support as a contact member is brought into contact with the surface of the mold to which the curable composition for imprints of the present invention has been applied (the surface on which the curable film has been formed). That is, in the contacting step, the curable composition for imprints of the present invention is present between the application member and the contacting member. The details of the support and the mold are as described above.

[0116] When the curable composition for imprints (curable film) of the present invention applied to a member to be applied is brought into contact with a contact member, the pressing pressure is preferably 1 MPa or less. By making the pressing pressure 1 MPa or less, the support and the mold are less likely to deform, and the pattern accuracy tends to improve. In addition, it is also preferable because the pressing force is low, which tends to enable the device to be made smaller. It is also preferable that the contact between the curable film and the contact member is carried out in an atmosphere containing helium gas or a condensable gas, or both helium gas and a condensable gas.

[0117] [Curing process] The method for producing an imprint pattern of the present invention includes a curing step of converting the above-mentioned curable composition for imprints into a cured product. The curing step is performed after the contacting step and before the peeling step. The method for producing a cured product of the present invention includes a step of curing the curable composition for imprints obtained by the method for producing a curable composition for imprints of the present invention. The curing step can be carried out by the same method as the curing step in the method for producing an imprint pattern of the present invention. In addition, the cured product is preferably in a state in which the mold has been peeled off by the peeling step described below. The curing method may be curing by heating, curing by exposure to light, or the like, and may be determined depending on the type of polymerization initiator contained in the curable composition for imprints, etc., but curing by exposure to light is preferred. For example, when the polymerization initiator is a photopolymerization initiator, the curable composition for imprints can be cured by exposure to light in the curing step.

[0118] The exposure wavelength is not particularly limited and may be determined depending on the polymerization initiator, and for example, ultraviolet light or the like can be used. The exposure light source may be determined depending on the exposure wavelength, and examples thereof include g-line (wavelength 436 nm), h-line (wavelength 405 nm), i-line (wavelength 365 nm), broadband light (light containing at least two types of light of wavelengths selected from the group consisting of three wavelengths of g, h, and i-line and light of a wavelength shorter than i-line. For example, a high-pressure mercury lamp when no optical filter is used may be mentioned.), semiconductor laser (wavelengths 830 nm, 532 nm, 488 nm, 405 nm, etc.), metal halide lamp, excimer laser, KrF excimer laser (wavelength 248 nm), ArF excimer laser (wavelength 193 nm), F2 excimer laser (wavelength 157 nm), extreme ultraviolet ray; EUV (wavelength 13.6 nm), electron beam, etc. Of these, exposure using i-line or broadband light is preferred.

[0119] The amount of irradiation (exposure amount) during exposure may be sufficiently greater than the minimum amount of irradiation required for curing the curable composition for imprints. The amount of irradiation required for curing the curable composition for imprints can be appropriately determined by examining the amount of consumption of unsaturated bonds in the curable composition for imprints, etc. The exposure dose is, for example, 5 to 1,000 mJ / cm 2 The range is preferably 10 to 500 mJ / cm 2 It is more preferable to set the range of The exposure illuminance is not particularly limited and may be selected depending on the relationship with the light source, but is preferably 1 to 500 mW / cm 2 The range is preferably 10 to 400 mW / cm2 It is more preferable to set the range of The exposure time is not particularly limited and may be determined in consideration of the exposure illuminance according to the amount of exposure, but is preferably 0.01 to 10 seconds, and more preferably 0.5 to 1 second. The temperature of the support during exposure is usually room temperature, but exposure may be performed while heating in order to enhance reactivity. As a pre-exposure step, a vacuum state is used to prevent the inclusion of air bubbles, suppress a decrease in reactivity due to the inclusion of oxygen, and improve the adhesion between the mold and the curable composition for imprints. Therefore, light irradiation may be performed in a vacuum state. The preferred degree of vacuum during exposure is 10 -1 The pressure ranges from Pa to atmospheric pressure.

[0120] After the exposure, the curable composition for imprints may be heated as necessary. The heating temperature is preferably 150 to 280° C., and more preferably 200 to 250° C. The heating time is preferably 5 to 60 minutes, and more preferably 15 to 45 minutes. In addition, in the curing step, only the heating step may be performed without performing exposure. For example, when the polymerization initiator is a thermal polymerization initiator, the curable composition for imprints can be cured by performing heating in the curing step. In this case, the preferred aspects of the heating temperature and heating time are the same as those in the case where heating is performed after exposure. The heating means is not particularly limited, and may be the same heating means as used in the drying step described above.

[0121] [Peeling process] The method for producing an imprint pattern of the present invention includes a peeling step of peeling the mold and the cured product. In the peeling step, the cured product obtained in the curing step is peeled off from the mold, and a patterned cured product (also referred to as a "cured product pattern") is obtained to which the pattern of the mold has been transferred. The obtained cured product pattern can be used for various applications as described below. The present invention is particularly advantageous in that it can form a fine cured product pattern of nano-order, and further, can form a cured product pattern having a size of 50 nm or less, particularly 30 nm or less. The lower limit of the size of the cured product pattern is not particularly specified, but can be, for example, 1 nm or more. The peeling method is not particularly limited, and for example, a mechanical peeling device known in the imprint pattern manufacturing method can be used.

[0122] (Devices, device manufacturing methods, and applications of cured material patterns) The device of the present invention includes the cured product of the present invention. The device of the present invention can be obtained, for example, by the following method for producing the device of the present invention. The device manufacturing method of the present invention includes the imprint pattern manufacturing method of the present invention. Specifically, examples of the method include a device manufacturing method in which a pattern (cured product pattern) formed by the imprint pattern manufacturing method of the present invention is used as a permanent film for use in liquid crystal display devices (LCDs) and the like, or as an etching resist (lithography mask) for manufacturing semiconductor elements. In particular, the present invention discloses a method for producing a circuit board, which includes a step of obtaining a pattern (cured product pattern) by the imprint pattern production method of the present invention, and a method for producing a device including the circuit board. Furthermore, a method for producing a circuit board according to a preferred embodiment of the present invention may include a step of performing etching or ion implantation on a substrate using the pattern (cured product pattern) obtained by the pattern formation method as a mask, and a step of forming an electronic component. The circuit board is preferably a semiconductor element. That is, the present invention discloses a method for producing a semiconductor device, which includes the imprint pattern production method of the present invention. Furthermore, the present invention discloses a method for producing a device, which includes a step of obtaining a circuit board by the circuit board production method, and a step of connecting the circuit board to a control mechanism that controls the circuit board. Furthermore, by forming a grid pattern on a glass substrate of a liquid crystal display device using the method for producing an imprint pattern of the present invention, a polarizing plate with a large screen size (for example, over 55 inches or 60 inches) with little reflection or absorption can be produced inexpensively. That is, the present invention discloses a method for producing a polarizing plate including the method for producing an imprint pattern of the present invention, and a method for producing a device including the polarizing plate. For example, the polarizing plates described in JP 2015-132825 A and WO 2011 / 132649 A can be produced. Note that 1 inch is 25.4 mm.

[0123] The pattern (cured product pattern) produced by the method for producing an imprint pattern of the present invention is also useful as an etching resist (lithography mask). That is, the present invention discloses a method for producing a device, which includes the method for producing an imprint pattern of the present invention and utilizes the obtained cured product pattern as an etching resist. When the cured product pattern is used as an etching resist, a pattern (cured product pattern) is first formed on a support by applying the method for producing an imprint pattern of the present invention, and the support is etched using the obtained cured product pattern as an etching mask. A pattern conforming to the shape of the desired cured product pattern can be formed on the support by etching using an etching gas such as hydrogen fluoride in the case of wet etching or CF4 in the case of dry etching.

[0124] Furthermore, a pattern (cured product pattern) produced by the method for producing an imprint pattern of the present invention can also be preferably used for producing recording media such as magnetic disks, light-receiving elements such as solid-state imaging elements, light-emitting elements such as LEDs (light emitting diodes) and organic EL (organic electroluminescence), optical devices such as liquid crystal displays (LCDs), optical components such as diffraction gratings, relief holograms, optical waveguides, optical filters, and microlens arrays, members for flat panel displays such as thin film transistors, organic transistors, color filters, anti-reflection films, polarizing plates, polarizing elements, optical films, and pillar materials, nanobiodevices, immunoassay chips, deoxyribonucleic acid (DNA) separation chips, microreactors, photonic liquid crystals, and guide patterns for fine pattern formation using self-organization of block copolymers (directed self-assembly, DSA), and the like. That is, the present invention discloses a method for manufacturing these devices, which includes a method for manufacturing the imprint pattern of the present invention.

[0125] <Composition for forming adhesive layer> As described above, by providing an adhesion layer between the support and the curable composition for imprints, effects such as improved adhesion between the support and the curable composition layer for imprints can be obtained. In the present invention, the adhesion layer is obtained by applying the composition for forming an adhesion layer onto the support in the same manner as the curable composition for imprints, and then curing the composition. Each component of the composition for forming an adhesion layer will be described below.

[0126] The composition for forming the adhesive layer contains a curable component. The curable component is a component that constitutes the adhesive layer, and may be either a polymer component (e.g., molecular weight over 1000) or a low molecular component (e.g., molecular weight less than 1000). Specific examples include resins and crosslinking agents. These may be used alone or in combination of two or more.

[0127] The total content of the curable components in the composition for forming the adhesive layer is not particularly limited, but is preferably 50% by mass or more in the total solid content, more preferably 70% by mass or more in the total solid content, and even more preferably 80% by mass or more in the total solid content. The upper limit is not particularly limited, but is preferably 99.9% by mass or less.

[0128] The concentration of the curable component in the composition for forming the adhesive layer (including the solvent) is not particularly limited, but is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, and even more preferably 0.1% by mass or more. The upper limit is preferably 10% by mass or less, more preferably 5% by mass or less, even more preferably 1% by mass or less, and even more preferably less than 1% by mass.

[0129] 〔resin〕 The resin in the composition for forming the adhesive layer may be any known resin. The resin used in the present invention preferably has at least one of a radical polymerizable group and a polar group, and more preferably has both a radical polymerizable group and a polar group.

[0130] By having a radical polymerizable group, an adhesive layer having excellent strength can be obtained. In addition, by having a polar group, the adhesiveness to the support can be improved. In addition, when a crosslinking agent is blended, the crosslinked structure formed after curing becomes stronger, and the strength of the obtained adhesive layer can be improved.

[0131] The radical polymerizable group preferably contains an ethylenically unsaturated bond-containing group.The ethylenically unsaturated bond-containing group includes a (meth)acryloyl group (preferably a (meth)acryloyloxy group, a (meth)acryloylamino group), a vinyl group, a vinyloxy group, an allyl group, a methylallyl group, a propenyl group, a butenyl group, a vinylphenyl group, and a cyclohexenyl group, and preferably a (meth)acryloyl group or a vinyl group, more preferably a (meth)acryloyl group, and further preferably a (meth)acryloyloxy group.The ethylenically unsaturated bond-containing group defined here is referred to as Et.

[0132] In addition, the polar group is preferably at least one of acyloxy group, carbamoyloxy group, sulfonyloxy group, acyl group, alkoxycarbonyl group, acylamino group, carbamoyl group, alkoxycarbonylamino group, sulfonamide group, phosphoric acid group, carboxy group and hydroxy group, more preferably at least one of alcoholic hydroxy group, phenolic hydroxy group and carboxy group, and even more preferably alcoholic hydroxy group or carboxy group. The polar group defined here is called polar group Po. The polar group is preferably a non-ionic group.

[0133] The resin in the adhesive layer forming composition may further contain a cyclic ether group. Examples of the cyclic ether group include an epoxy group and an oxetanyl group, and the epoxy group is preferred. The cyclic ether group defined here is referred to as a cyclic ether group Cyt.

[0134] Examples of the resin include (meth)acrylic resin, vinyl resin, novolac resin, phenol resin, melamine resin, urea resin, epoxy resin, and polyimide resin, and it is preferably at least one of (meth)acrylic resin, vinyl resin, and novolac resin.

[0135] The weight average molecular weight of the resin is preferably at least 4000, more preferably at least 6000, and even more preferably at least 8000. The upper limit is preferably at most 1,000,000, and may be at most 500,000.

[0136] The above resin preferably has at least one structural unit represented by the following formulas (1) to (3).

[0137] [ka]

[0138] In the formula, R 1 and R 2 R is each independently a hydrogen atom or a methyl group. 21 and R 3 Each of L is independently a substituent. 1 , L 2 and L 3 are each independently a single bond or a linking group. n2 is an integer of 0 to 4. n3 is an integer of 0 to 3. Q 1 is an ethylenically unsaturated bond-containing group or a cyclic ether group. 2 is an ethylenically unsaturated bond-containing group, a cyclic ether group or a polar group.

[0139] R 1 and R 2 is preferably a methyl group.

[0140] R 21 and R 3 are each preferably independently the above-mentioned substituents.

[0141] R 21When there are a plurality of rings, they may be linked together to form a cyclic structure. In this specification, the term "linked" includes not only the mode of being linked and continuous, but also the mode of condensation (condensed ring) by losing some atoms. In addition, unless otherwise specified, the linked cyclic structure may contain an oxygen atom, a sulfur atom, or a nitrogen atom (amino group). Examples of the cyclic structure that is formed include an aliphatic hydrocarbon ring (examples of which are hereinafter referred to as ring Cf) (e.g., cyclopropyl group, cyclobutyl group, cyclopentyl group, cyclohexyl group, cyclopropenyl group, cyclobutenyl group, cyclopentenyl group, cyclohexenyl group, etc.), an aromatic hydrocarbon ring (examples of which are hereinafter referred to as ring Cr) (e.g., benzene ring, naphthalene ring, anthracene ring, phenanthrene ring, etc.), a nitrogen-containing heterocycle (examples of which are hereinafter referred to as ring Cn) (e.g., pyrrole ring, imidazole ring, pyrrole ring, etc.), and an aromatic hydrocarbon ring (examples of which are hereinafter referred to as ring Cn) (e.g., cyclopropyl group, cyclobutyl group, cyclopentyl group, cyclohexyl group, cyclopropenyl group, cyclobutenyl group, cyclopentenyl group, cyclohexenyl group, etc.), an aromatic hydrocarbon ring (examples of which are hereinafter referred to as ring Cr) (e.g., benzene ring, naphthalene ring, anthracene ring, phenanthrene ring, etc.), and an aromatic hydrocarbon ring (examples of which are hereinafter referred to as ring Cn) (e.g., pyrrole ring, imidazole ring, pyrrole ring, etc.). Examples of such heterocyclic rings include a pyrazole ring, a pyridine ring, a pyrroline ring, a pyrrolidine ring, an imidazolidine ring, a pyrazolidine ring, a piperidine ring, a piperazine ring, a morpholine ring, etc.), an oxygen-containing heterocyclic ring (examples of which are referred to as Ring Co below) (a furan ring, a pyran ring, an oxirane ring, an oxetane ring, a tetrahydrofuran ring, a tetrahydropyran ring, a dioxane ring, etc.), and a sulfur-containing heterocyclic ring (examples of which are referred to as Ring Cs below) (a thiophene ring, a thiirane ring, a thietane ring, a tetrahydrothiophene ring, a tetrahydrothiopyran ring, etc.).

[0142] R 3 When there are a plurality of rings, they may be linked together to form a ring structure. Examples of the ring structure that may be formed include Cf, ring Cr, ring Cn, ring Co, and ring Cs.

[0143] L 1 , L 2 , L 3are each preferably independently a single bond or a linking group L described later. Among them, a single bond, or an alkylene group or (oligo)alkyleneoxy group defined by the linking group L is preferred, and an alkylene group is more preferred. The linking group L preferably has a polar group Po as a substituent. Also preferred is an embodiment in which the alkylene group has a hydroxy group as a substituent. In this specification, "(oligo)alkyleneoxy group" means a divalent linking group having one or more "alkyleneoxy" structural units. The number of carbon atoms in the alkylene chain in the structural units may be the same or different for each structural unit.

[0144] n2 is preferably 0 or 1, and more preferably 0. n3 is preferably 0 or 1, and more preferably 0.

[0145] Q 1 is preferably an ethylenically unsaturated bond-containing group Et.

[0146] Q 2 is preferably a polar group, and more preferably an alkyl group having an alcoholic hydroxy group.

[0147] The above resin may further contain at least one of the following structural units (11), (21), and (31). In particular, in the resin included in the present invention, the structural unit (11) is preferably combined with the structural unit (1), the structural unit (21) is preferably combined with the structural unit (2), and the structural unit (31) is preferably combined with the structural unit (3).

[0148] [ka]

[0149] In the formula, R 11 and R 22 R is each independently a hydrogen atom or a methyl group. 17 is a substituent. 27 is a substituent. n21 is an integer of 0 to 5. R 31is a substituent, and n31 is an integer of 0 to 3.

[0150] R 11 and R 22 is preferably a methyl group.

[0151] R 17 R is preferably a group containing a polar group or a group containing a cyclic ether group. 17 When R is a group containing a polar group, it is preferably a group containing the above-mentioned polar group Po, and more preferably is the above-mentioned polar group Po or a substituent substituted with the above-mentioned polar group Po. 17 When is a group containing a cyclic ether group, it is preferably a group containing the above-mentioned cyclic ether group Cyt, and more preferably a substituent substituted with the above-mentioned cyclic ether group Cyt.

[0152] R 27 is a known substituent, and R 27 At least one of R is preferably a polar group. n21 is preferably 0 or 1, and more preferably 0. 27 When there are a plurality of rings, they may be linked together to form a cyclic structure. Examples of the cyclic structure that may be formed include a Cf ring, a Cr ring, a Cn ring, a Co ring, and a Cs ring.

[0153] R 31 is preferably a known substituent. n31 is an integer of 0 to 3, preferably 0 or 1, and more preferably 0. R 31 When there are a plurality of rings, they may be linked together to form a cyclic structure. Examples of the cyclic structure that may be formed include a Cf ring, a Cr ring, a Cn ring, a Co ring, and a Cs ring.

[0154] Examples of the linking group L include an alkylene group (preferably having 1 to 24 carbon atoms, more preferably having 1 to 12 carbon atoms, and even more preferably having 1 to 6 carbon atoms), an alkenylene group (preferably having 2 to 12 carbon atoms, more preferably having 2 to 6 carbon atoms, and even more preferably having 2 to 3 carbon atoms), an (oligo)alkyleneoxy group (the number of carbon atoms in the alkylene group in one constitutional unit is preferably 1 to 12, more preferably having 1 to 6, and even more preferably having 1 to 3 carbon atoms; the number of repetitions is preferably 1 to 50, more preferably having 1 to 40, and even more preferably having 1 to 30 carbon atoms), an arylene group (preferably having 6 to 22 carbon atoms, more preferably having 6 to 18 carbon atoms, and even more preferably having 6 to 10 carbon atoms), an oxygen atom, a sulfur atom, a sulfonyl group, a carbonyl group, a thiocarbonyl group, -NR N The alkylene group, the alkenylene group, and the alkyleneoxy group may have a substituent. For example, the alkylene group may have a hydroxy group.

[0155] The linking chain length of the linking group L is preferably 1 to 24, more preferably 1 to 12, and further preferably 1 to 6. The linking chain length means the number of atoms located on the shortest path among the atomic groups involved in the linking. For example, in the case of -CH2-(C=O)-O-, the linking chain length is 3.

[0156] The alkylene group, alkenylene group, and (oligo)alkyleneoxy group defined by the linking group L may be chain-like or cyclic, and may be straight-chain or branched.

[0157] The atoms constituting the linking group L preferably include carbon atoms and hydrogen atoms, and if necessary, heteroatoms (at least one selected from oxygen atoms, nitrogen atoms, and sulfur atoms). The number of carbon atoms in the linking group is preferably 1 to 24, more preferably 1 to 12, and even more preferably 1 to 6. The number of hydrogen atoms may be determined according to the number of carbon atoms, etc. The number of heteroatoms is preferably 0 to 12, more preferably 0 to 6, and even more preferably 0 to 3 for each of the oxygen atoms, nitrogen atoms, and sulfur atoms, independently.

[0158] The synthesis of the above resin may be performed according to a conventional method. For example, a resin having a structural unit of formula (1) can be appropriately synthesized by a known method related to addition polymerization of olefins. A resin having a structural unit of formula (2) can be appropriately synthesized by a known method related to addition polymerization of styrene. A resin having a structural unit of formula (3) can be appropriately synthesized by a known method related to the synthesis of phenolic resins.

[0159] The above resins may be used alone or in combination.

[0160] In addition to the above, the resin as the curable component may be one described in paragraphs 0016 to 0079 of WO 2016 / 152600, paragraphs 0025 to 0078 of WO 2016 / 148095, paragraphs 0015 to 0077 of WO 2016 / 031879, or paragraphs 0015 to 0057 of WO 2016 / 027843, the contents of which are incorporated herein by reference.

[0161] [Crosslinking Agent] The crosslinking agent in the adhesive layer forming composition is not particularly limited as long as it can progress curing by crosslinking reaction. In the present invention, the crosslinking agent is preferably one that forms a crosslinked structure by reacting with the polar group of the resin. By using such a crosslinking agent, the resin is more strongly bonded, and a stronger film can be obtained.

[0162] Examples of crosslinking agents include epoxy compounds (compounds having an epoxy group), oxetanyl compounds (compounds having an oxetanyl group), alkoxymethyl compounds (compounds having an alkoxymethyl group), methylol compounds (compounds having a methylol group), and blocked isocyanate compounds (compounds having a blocked isocyanate group). Of these, alkoxymethyl compounds (compounds having an alkoxymethyl group) are preferred because they are capable of forming strong bonds at low temperatures.

[0163] [Other ingredients] The composition for forming an adhesive layer may contain other components in addition to the above components.

[0164] Specifically, the composition may contain one or more of a solvent, a thermal acid generator, an alkylene glycol compound, a polymerization initiator, a polymerization inhibitor, an antioxidant, a leveling agent, a thickener, a surfactant, etc. As for the above components, the components described in JP-A-2013-036027, JP-A-2014-090133, and JP-A-2013-189537 can be used. The contents and the like can also be taken into consideration in the above publications.

[0165] -solvent- In the present invention, the composition for forming the adhesion layer preferably contains a solvent (hereinafter, also referred to as "solvent for adhesion layer"). For example, the solvent is preferably a compound that is liquid at 23°C and has a boiling point of 250°C or less. The composition for forming the adhesion layer preferably contains 99.0% by mass or more of the solvent for the adhesion layer, more preferably 99.2% by mass or more, and may contain 99.4% by mass or more. That is, the composition for forming the adhesion layer preferably has a total solid content concentration of 1% by mass or less, more preferably 0.8% by mass or less, and even more preferably 0.6% by mass or less. In addition, the lower limit is preferably more than 0% by mass, more preferably 0.001% by mass or more, even more preferably 0.01% by mass or more, and even more preferably 0.1% by mass or more. By setting the ratio of the solvent in the above range, the film thickness during film formation tends to be kept thin, and the pattern formability during etching processing tends to be improved.

[0166] The adhesive layer-forming composition may contain only one type of solvent, or may contain two or more types. When two or more types are contained, the total amount thereof is preferably within the above range.

[0167] The boiling point of the solvent for the adhesive layer is preferably 230° C. or less, more preferably 200° C. or less, even more preferably 180° C. or less, even more preferably 160° C. or less, and even more preferably 130° C. or less. The lower limit is preferably 23° C., and more preferably 60° C. or more. By setting the boiling point within the above range, the solvent can be easily removed from the adhesive layer, which is preferable.

[0168] The solvent for the adhesive layer is preferably an organic solvent. The solvent is preferably a solvent having at least one of an ester group, a carbonyl group, a hydroxyl group, and an ether group. Among them, it is preferable to use an aprotic polar solvent.

[0169] Among the solvents for the adhesion layer, preferred solvents include alkoxy alcohols, propylene glycol monoalkyl ether carboxylates, propylene glycol monoalkyl ethers, lactates, acetates, alkoxypropionates, chain ketones, cyclic ketones, lactones, and alkylene carbonates, with propylene glycol monoalkyl ethers and lactones being particularly preferred.

[0170] <Liquid film forming composition> In the present invention, it is also preferable to form a liquid film on the adhesive layer using a liquid film-forming composition containing a radically polymerizable compound that is liquid at 23°C and 1 atm. In the present invention, the liquid film is obtained by applying the liquid film-forming composition on a support in the same manner as the curable composition for imprints, and then drying the composition. By forming such a liquid film, there is an effect that the adhesion between the support and the curable composition for imprints is further improved, and the wettability of the curable composition for imprints on the support is also improved. The liquid film-forming composition will be described below.

[0171] The viscosity of the liquid film forming composition is preferably 1000 mPa·s or less, more preferably 800 mPa·s or less, even more preferably 500 mPa·s or less, and even more preferably 100 mPa·s or less. The lower limit of the viscosity is not particularly limited, but can be, for example, 1 mPa·s or more. The viscosity is measured according to the following method.

[0172] Viscosity is measured using a Toki Sangyo Co., Ltd. E-type rotational viscometer RE85L with a standard cone rotor (1°34' x R24) and the sample cup is adjusted to a temperature of 23°C. The unit is mPa·s. Other details regarding the measurement are in accordance with JIS Z8803:2011. Two samples are prepared for each level, and each is measured three times. The arithmetic average of a total of six measurements is used as the evaluation value.

[0173] [Radically polymerizable compound A] The liquid film forming composition contains a radically polymerizable compound (radical polymerizable compound A) that is liquid at 23° C. and 1 atmospheric pressure.

[0174] The viscosity of the radical polymerizable compound A at 23° C. is preferably 1 to 100,000 mPa·s. The lower limit is preferably 5 mPa·s or more, and more preferably 11 mPa·s or more. The upper limit is preferably 1,000 mPa·s or less, and more preferably 600 mPa·s or less.

[0175] The radical polymerizable compound A may be a monofunctional radical polymerizable compound having only one radical polymerizable group in one molecule, or may be a polyfunctional radical polymerizable compound having two or more radical polymerizable groups in one molecule. A monofunctional radical polymerizable compound and a polyfunctional radical polymerizable compound may be used in combination. Among them, the radical polymerizable compound A contained in the liquid film forming composition preferably contains a polyfunctional radical polymerizable compound, more preferably contains a radical polymerizable compound having 2 to 5 radical polymerizable groups in one molecule, further preferably contains a radical polymerizable compound having 2 to 4 radical polymerizable groups in one molecule, and particularly preferably contains a radical polymerizable compound having two radical polymerizable groups in one molecule, for the reason of suppressing pattern collapse.

[0176] The radical polymerizable compound A preferably contains at least one of an aromatic ring (preferably having 6 to 22 carbon atoms, more preferably having 6 to 18 carbon atoms, and even more preferably having 6 to 10 carbon atoms) and an alicyclic ring (preferably having 3 to 24 carbon atoms, more preferably having 3 to 18 carbon atoms, and even more preferably having 3 to 6 carbon atoms), and even more preferably contains an aromatic ring. The aromatic ring is preferably a benzene ring. The molecular weight of the radical polymerizable compound A is preferably 100 to 900.

[0177] The radically polymerizable group contained in the radically polymerizable compound A includes ethylenically unsaturated bond-containing groups such as a vinyl group, an allyl group, and a (meth)acryloyl group, and is preferably a (meth)acryloyl group.

[0178] The radically polymerizable compound A is also preferably a compound represented by the following formula (I-1).

[0179] [ka]

[0180] L 20 is a 1+q2-valent linking group, and examples thereof include a 1+q2-valent group having an alkane structure (preferably having 1 to 12 carbon atoms, more preferably having 1 to 6 carbon atoms, and even more preferably having 1 to 3 carbon atoms), a group having an alkene structure (preferably having 2 to 12 carbon atoms, more preferably having 2 to 6 carbon atoms, and even more preferably having 2 to 3 carbon atoms), a group having an aryl structure (preferably having 6 to 22 carbon atoms, more preferably having 6 to 18 carbon atoms, and even more preferably having 6 to 10 carbon atoms), a group having a heteroaryl structure (preferably having 1 to 22 carbon atoms, more preferably having 1 to 18 carbon atoms, and even more preferably having 1 to 10 carbon atoms, examples of heteroatoms include nitrogen atoms, sulfur atoms, and oxygen atoms, and 5-membered rings, 6-membered rings, and 7-membered rings are preferred), or a linking group containing a group combining these. Examples of groups combining two aryl groups include groups having structures such as biphenyl, diphenylalkane, biphenylene, and indene. Examples of the combination of a group having a heteroaryl structure and a group having an aryl structure include groups having structures such as indole, benzimidazole, quinoxaline, and carbazole.

[0181] L 20 is preferably a linking group containing at least one selected from a group having an aryl structure and a group having a heteroaryl structure, and more preferably a linking group containing a group having an aryl structure.

[0182] R 21 and R 22 each independently represents a hydrogen atom or a methyl group.

[0183] L 21 and L 22 each independently represents a single bond or the above linking group L, and is preferably a single bond or an alkylene group.

[0184] L 20 and L 21 Or L 22 may be bonded to form a ring with or without a linking group L. 20 , L 21 and L 22 may have a substituent. A plurality of the substituents may be bonded to form a ring. When there are a plurality of the substituents, they may be the same or different.

[0185] q2 represents an integer of 0 to 5, preferably an integer of 0 to 3, more preferably an integer of 0 to 2, further preferably 0 or 1, and particularly preferably 1.

[0186] As the radical polymerizable compound A, the compounds described in paragraphs

[0017] to

[0024] and the examples of JP2014-090133A, the compounds described in paragraphs

[0024] to

[0089] of JP2015-009171A, the compounds described in paragraphs

[0023] to

[0037] of JP2015-070145A, and the compounds described in paragraphs

[0012] to

[0039] of WO2016 / 152597 can also be used.

[0187] The content of the radical polymerizable compound A in the liquid film forming composition is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, and even more preferably 0.1% by mass or more. The upper limit is preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 1% by mass or less.

[0188] The content of the radical polymerizable compound A in the solid content of the liquid film forming composition is preferably 50% by mass or more, more preferably 75% by mass or more, and even more preferably 90% by mass or more. The upper limit may be 100% by mass. Only one type of radical polymerizable compound A may be used, or two or more types may be used. When two or more types are used, the total amount thereof is preferably within the above range.

[0189] It is also preferable that the solid content of the liquid film forming composition is substantially composed of only the radical polymerizable compound A. When the solid content of the liquid film forming composition is substantially composed of only the radical polymerizable compound A, it means that the content of the radical polymerizable compound A in the solid content of the liquid film forming composition is 99.9 mass% or more, more preferably 99.99 mass% or more, and further preferably composed of only the polymerizable compound A.

[0190] 〔solvent〕 The liquid film forming composition preferably contains a solvent (hereinafter, sometimes referred to as "liquid film solvent"). Examples of the liquid film solvent include those described in the above section on the adhesive layer solvent, and these can be used. The liquid film forming composition preferably contains 90% by mass or more of the liquid film solvent, more preferably 99% by mass or more, and may contain 99.99% by mass or more.

[0191] The boiling point of the liquid membrane solvent is preferably 230° C. or less, more preferably 200° C. or less, even more preferably 180° C. or less, even more preferably 160° C. or less, and even more preferably 130° C. or less. The lower limit is preferably 23° C., and more preferably 60° C. or more. By setting the boiling point within the above range, the solvent can be easily removed from the liquid membrane, which is preferable.

[0192] [Radical Polymerization Initiator] The liquid film forming composition may contain a radical polymerization initiator. Examples of the radical polymerization initiator include a thermal radical polymerization initiator and a photoradical polymerization initiator, and a photoradical polymerization initiator is preferable. Any known compound can be used as the photoradical polymerization initiator. Examples of the photoradical polymerization initiator include halogenated hydrocarbon derivatives (e.g., compounds having a triazine skeleton, compounds having an oxadiazole skeleton, compounds having a trihalomethyl group, etc.), acylphosphine compounds, hexaarylbiimidazole compounds, oxime compounds, organic peroxides, thio compounds, ketone compounds, aromatic onium salts, acetophenone compounds, azo compounds, azide compounds, metallocene compounds, organic boron compounds, and iron arene complexes. For details of these, the descriptions in paragraphs 0165 to 0182 of JP 2016-027357 A can be referred to, and the contents of this specification are incorporated herein. Among these, acetophenone compounds, acylphosphine compounds, and oxime compounds are preferable. Commercially available products include IRGACURE-OXE01, IRGACURE-OXE02, IRGACURE-127, IRGACURE-819, IRGACURE-379, IRGACURE-369, IRGACURE-754, IRGACURE-1800, IRGACURE-651, IRGACURE-907, IRGACURE-TPO, IRGACURE-1173, and the like (all manufactured by BASF), Omnirad 184, Omnirad TPO H, Omnirad 819, Omnirad 1173 (all manufactured by IGM Resins BV).

[0193] When the radical polymerization initiator is contained, it is preferably 0.1 to 10 mass %, more preferably 1 to 8 mass %, and further preferably 2 to 5 mass % of the solid content of the liquid film forming composition. When two or more kinds of radical polymerization initiators are used, the total amount thereof is preferably within the above range.

[0194] [Other ingredients] The liquid film forming composition may contain, in addition to the above, one or more of polymerization inhibitors, antioxidants, leveling agents, thickeners, surfactants, and the like. EXAMPLES

[0195] The present invention will be described in more detail below with reference to examples. The materials, amounts used, ratios, processing contents, processing procedures, etc. shown in the following examples can be changed as appropriate without departing from the spirit of the present invention. Therefore, the scope of the present invention is not limited to the specific examples shown below. In the examples, unless otherwise specified, "parts" and "%" are based on mass, and the environmental temperature (room temperature) of each step is 23°C.

[0196] <Preparation of Curable Composition for Imprints> In each of the Examples and Comparative Examples, various compounds shown in the following table were mixed to prepare a curable composition for imprints or a comparative composition. In each composition, a component marked with "-" was not added. This was filtered through a 0.05 μm UPE (ultra-high molecular weight polyethylene resin) filter, a 0.02 μm Nylon filter, and a 0.005 μm UPE filter in this order to prepare a curable composition for imprints or a comparative composition. In the table, the column "Amount of radically polymerizable group" shows the molar amount of the radically polymerizable group relative to the total solid content of the composition.

[0197] [Table 1]

[0198] [Table 2]

[0199] [Table 3]

[0200] Details of each component listed in the table are as follows.

[0201] [Compound A] A-1: The following synthetic product, radical polymerizable group value: 1,200 g / mol A-2: The synthetic product below, radical polymerizable group value: 12,000 g / mol, however, the values ​​in the table are the amounts added as a solution containing 50% by mass of A-2. A-3: A compound represented by the following formula (A-3). The subscript in parentheses indicates the number of repetitions. Radical polymerizable group value: 293 g / mol A-4: The following synthetic product, radical polymerizable group value: 2,083 g / mol A-5: A-BPE-10 (product name, manufactured by Shin-Nakamura Chemical Co., Ltd.), radical polymerizable group value: 389 g / mol [ka]

[0202] -Synthesis of Compound A-1- Methyl silicone resin KR-500 (trade name, manufactured by Shin-Etsu Chemical Co., Ltd.) (110.8 parts), 2-hydroxyethyl acrylate (58.1 parts), and paratoluenesulfonic acid monohydrate (0.034 parts) were mixed, and the mixture was heated to 120°C while bubbling nitrogen gas containing 5% oxygen, and the mixture was reacted for 3 hours while stirring and distilling off the methanol produced by the condensation reaction, to obtain 153.9 parts of A-1. The physical properties of the obtained compound were as follows, and it was confirmed that the compound had an alkoxysilyl group in the molecule and contained 10% by mass or more of silicon atoms. 1H-NMR (300 MHz, CDCl3) δ (ppm): 6.43 (m, CH=C), 6.13 (m, C=CH-C=O), 5.83 (m, CH=C), 4.25 (br, CH2-OC=O), 3.96 (br, CH2-O-Si), 3.50 (s, Si-OCH3), 0.15 (s, Si-CH3). The weight-average molecular weight was measured to be 1650.

[0203] -Synthesis of Compound A-2- A reaction vessel equipped with a stirrer, a thermometer, a dropping funnel, a cooling tube and a nitrogen gas inlet was charged with phenyltrimethoxysilane (20.1 parts), dimethyldimethoxysilane (24.4 parts), and n-butyl acetate (107.7 parts), and the mixture was heated to 80° C. while stirring under nitrogen gas aeration. Next, a mixture containing methyl methacrylate (14.5 parts), n-butyl methacrylate (2 parts), cyclohexyl methacrylate (105 parts), acrylic acid (7.5 parts), 3-methacryloyloxypropyltrimethoxysilane (4.5 parts), 2-hydroxyethyl methacrylate (15 parts), n-butyl acetate (15 parts), and tert-butylperoxy-2-ethylhexanoate (6 parts) was added dropwise to the reaction vessel over 4 hours at the same temperature while stirring under nitrogen gas aeration. After stirring for an additional 2 hours at the same temperature, a mixture of isopropyl phosphate (0.05 parts) and deionized water (12.8 parts) was added dropwise to the reaction vessel over 5 minutes, and the mixture was stirred for 4 hours at the same temperature to allow the hydrolysis and condensation reaction of phenyltrimethoxysilane, dimethyldimethoxysilane, and 3-methacryloyloxypropyltrimethoxysilane to proceed. 1When analyzed by H-NMR, it was found that almost 100% of the methoxy groups in the trimethoxysilyl groups of the silane monomer in the reaction vessel were hydrolyzed. Then, by stirring at the same temperature for 10 hours, a vinyl-based polymer was obtained as a reaction product with a residual amount of tert-butylperoxy-2-ethylhexanoate of 0.1 mass% or less. Next, 162.5 parts of methyl silicone resin KR-515 (trade name, manufactured by Shin-Etsu Chemical Co., Ltd.) was added to 307 parts of the obtained vinyl-based polymer and stirred for 5 minutes, and then 27.5 parts of deionized water was added and stirred at 80°C for 4 hours to carry out a hydrolysis condensation reaction of the reaction product and polysiloxane. The reaction product was distilled for 2 hours under reduced pressure of 10 to 300 kPa at 40 to 60°C to remove the produced methanol and water, and then 150 parts of methyl ethyl ketone (MEK) and 27.3 parts of n-butyl acetate were added to obtain 600 parts of compound A-2 with a non-volatile content of 50.0%. The weight average molecular weight of compound A-2 was measured to be 2,000.

[0204] -Synthesis of Compound A-4- In a glass flask equipped with a cooling tube and a stirring blade made of Teflon (registered trademark), methyl silicone resin X-40-9225 (trade name, manufactured by Shin-Etsu Chemical Co., Ltd.) (110.8 parts), 2-hydroxyethyl acrylate (58.1 parts), and sulfuric acid (0.0034 parts) were mixed, heated to 120 ° C., and the mixture was stirred for 10 hours while distilling off the methanol produced by the condensation reaction, to obtain 153.9 parts of A-4. The physical properties of the obtained compound were as follows, and it was confirmed that it was a photosensitive resin having a group having a curable functional group. 1 H-NMR (300 MHz, CDCl3) δ (ppm): 6.43 (m, CH=C), 6.13 (m, C=CH-C=O), 5.83 (m, CH=C), 4.25 (br, CH2-OC=O), 3.96 (br, CH2-O-Si), 3.50 (s, Si-OCH3), 0.15 (s, Si-CH3). The weight average molecular weight was measured to be 5100.

[0205] [Compound B (radical polymerization initiator)] ·B-1: Omnirad TPO H (manufactured by IGM Resins) ·B-2: Omnirad 819 (manufactured by IGM Resins) B-3: Irgacure OXE02 (BASF) ·B-4: Omnirad 2959 (manufactured by IGM Resins) ·B-5: Omnirad MBF (manufactured by IGM Resins)

[0206] [Specific compound] G-1 to G-16: Compounds having the following structures. G-1 to G-16 are compounds corresponding to compound C. H-1: A compound having the following structure. H-1 is not a compound C. In the following chemical formula, Bu represents a butyl group, Me represents a methyl group, and the subscripts in parentheses represent the number of repetitions. [ka] [ka]

[0207] [Additives] R-1 to R-3: Compounds having the following structures, in which the subscripts in parentheses indicate the number of repetitions. [ka]

[0208] 〔solvent〕 ·PGMEA: Propylene glycol monomethyl ether acetate

[0209] (evaluation) <Evaluation of releasability> The adhesive layer forming composition shown in Example 6 of JP 2014-024322 A was spin-coated on a silicon wafer and heated for 1 minute using a hot plate at 220°C to form an adhesive layer having a thickness of 5 nm. A pattern forming composition (curable composition for imprints or comparative composition) was applied onto the adhesive layer by spin-coating. The thickness of the layer made of the pattern forming composition was 50 μm. Then, in a helium atmosphere, an imprinting mold was pressed against the pattern-forming composition. The mold used was a quartz mold having lines and spaces with a line width of 15 nm, a depth of 30 nm, and a pitch of 60 nm. Then, an exposure dose of 100 mJ / cm was applied from the mold surface using an ultra-high pressure mercury lamp. 2 The pattern was then exposed to light so as to become 90° C., and the mold was then released to obtain a pattern made of a cured product of the pattern-forming composition. In the above pattern formation, the force required to release the quartz mold (mold release force F, unit: N) was measured. Evaluation was performed according to the following evaluation criteria, and the evaluation results are shown in the "Mold release property" column in the table. The mold release force was measured according to the method of the comparative example described in paragraphs 0102 to 0107 of JP2011-206977A. [Evaluation Criteria] A: The release force F was less than 17N. B: The release force F was 17N or more and less than 20N. C: The release force F was 20N or more and less than 23N. D: The release force F was 23 N or more.

[0210] <Evaluation of coating film stability> The film thickness (T1) of the film made of the pattern-forming composition immediately after preparation, obtained in the same manner as in the evaluation of the mold releasability described above, was measured. Furthermore, the wafer on which the film was formed was left at room temperature for 48 hours, and the film thickness (T2) was measured again. The difference in film thickness (ΔFT=│T1-T2│) between immediately after the film was formed and after 48 hours was confirmed. Evaluation was performed according to the following evaluation criteria from the ΔFT value. The evaluation results are shown in the column "Stability of coated film" in the table. The film thickness was measured by an ellipsometer. A: ΔFT≦0.1 nm B: 0.1 nm < ΔFT ≦ 0.3 nm C: 0.3 nm < ΔFT ≦ 0.5 nm D: 0.5 nm < ΔFT ≦ 1.0 nm

[0211] From the above results, it is evident that when the curable composition for imprints of the present invention is used, excellent releasability is achieved. The compositions according to Comparative Examples 1 and 2 do not contain compound C. In such an embodiment, it is clear that the releasability is poor.

[0212] In addition, an adhesion layer was formed on a silicon wafer using the adhesion layer forming composition in the same manner as in the evaluation of the above-mentioned mold releasability, and a line & space structure, a contact hole structure, a dual damascene structure, and a staircase structure were formed on the adhesion layer of the silicon wafer with the adhesion layer using the curable composition for imprints according to each Example. Then, using this pattern as an etching mask, the silicon wafer was dry etched, and each of the silicon wafers was used to fabricate a semiconductor device. There were no problems with the performance of any of the semiconductor devices. Furthermore, a semiconductor device was fabricated on a substrate having a SOC (spin-on carbon) layer in the same manner as above using the above-mentioned adhesion layer forming composition and the curable composition for imprints according to each Example. There were no problems with the performance of this semiconductor device either.

Claims

1. Compound A is a polymerizable compound having two or more radical polymerizable groups; Compound B which is a radical polymerization initiator; and compound C which is at least one selected from the group consisting of organopolysiloxanes having only one radically polymerizable group and no poly(oxyalkylene) group, organopolysiloxanes having only one radically polymerizable group and a poly(oxyalkylene) group, and organopolysiloxanes having no radically polymerizable group and a poly(oxyalkylene) group, The organopolysiloxane having only one radically polymerizable group and having a poly(oxyalkylene) group, and the organopolysiloxane having no radically polymerizable group and having a poly(oxyalkylene) group, each contain a structural unit represented by the following formula (S-2): Curable composition for imprints. 【Chemistry 1】 In formula (S-2), R represents a hydrocarbon group, and R S1 represents a group having a poly(oxyalkylene) group.

2. A polymerizable compound A having two or more radical polymerizable groups; Compound B which is a radical polymerization initiator; and compound C which is at least one selected from the group consisting of organopolysiloxanes having only one radically polymerizable group and no poly(oxyalkylene) group, organopolysiloxanes having only one radically polymerizable group and a poly(oxyalkylene) group, and organopolysiloxanes having no radically polymerizable group and a poly(oxyalkylene) group, The ratio of the total mass of the compound C to the total mass of the compound A contained in the composition is 0.2 to 20 mass%. Curable composition for imprints.

3. A polymerizable compound A having two or more radical polymerizable groups; Compound B which is a radical polymerization initiator; and compound C which is at least one selected from the group consisting of organopolysiloxanes having only one radically polymerizable group and no poly(oxyalkylene) group, organopolysiloxanes having only one radically polymerizable group and a poly(oxyalkylene) group, and organopolysiloxanes having no radically polymerizable group and a poly(oxyalkylene) group, The molar amount of the radical polymerizable group relative to the total solid content of the composition is 0.03 to 5.00 mol / g. Curable composition for imprints.

4. A polymerizable compound A having two or more radical polymerizable groups; Compound B which is a radical polymerization initiator; and compound C which is at least one selected from the group consisting of organopolysiloxanes having only one radically polymerizable group and no poly(oxyalkylene) group, organopolysiloxanes having only one radically polymerizable group and a poly(oxyalkylene) group, and organopolysiloxanes having no radically polymerizable group and a poly(oxyalkylene) group, The radical polymerizable group value of the compound A is 100 to 1,500. Curable composition for imprints.

5. A polymerizable compound A having two or more radical polymerizable groups; Compound B which is a radical polymerization initiator; and compound C which is at least one selected from the group consisting of organopolysiloxanes having only one radically polymerizable group and no poly(oxyalkylene) group, organopolysiloxanes having only one radically polymerizable group and a poly(oxyalkylene) group, and organopolysiloxanes having no radically polymerizable group and a poly(oxyalkylene) group, The poly(oxyalkylene) group contains an oxyalkylene group represented by the following formula (OA-1): Curable composition for imprints. 【Chemistry 2】 In formula (OA-1), R O1 and R O2 each independently represent a hydrogen atom or a methyl group, provided that both R O1 and R O2 are not methyl groups.

6. A polymerizable compound A having two or more radical polymerizable groups; Compound B which is a radical polymerization initiator; and compound C which is at least one selected from the group consisting of organopolysiloxanes having only one radically polymerizable group and no poly(oxyalkylene) group, organopolysiloxanes having only one radically polymerizable group and a poly(oxyalkylene) group, and organopolysiloxanes having no radically polymerizable group and a poly(oxyalkylene) group, The content of the poly(oxyalkylene) group in compound C is 1 to 50 mass %. Curable composition for imprints.

7. The curable composition for imprints according to any one of claims 1 to 6, wherein the radical polymerizable group in the organopolysiloxane having only one radical polymerizable group and no poly(oxyalkylene) group, and the radical polymerizable group in the organopolysiloxane having only one radical polymerizable group and having a poly(oxyalkylene) group, is an acryloyl group or a (meth)acryloyl group.

8. The curable composition for imprints according to any one of claims 1 to 7, wherein the alkylene group in the poly(oxyalkylene) group has 2 or 3 carbon atoms.

9. The curable composition for imprints according to any one of claims 1 to 8, wherein the compound C contains a repeating unit represented by the following formula (S-1): 【Chemistry 3】 In formula (S-1), each R independently represents a hydrocarbon group.

10. The curable composition for imprints according to any one of claims 2 to 6, wherein the organopolysiloxane having only one radically polymerizable group and having a poly(oxyalkylene) group, and the organopolysiloxane having no radically polymerizable group and having a poly(oxyalkylene) group, each contain a constitutional unit represented by the following formula (S-2): 【Chemistry 4】 In formula (S-2), R represents a hydrocarbon group; S1 represents a group having a poly(oxyalkylene) group.

11. The curable composition for imprints according to any one of claims 1 to 10, wherein the compound B is a photoradical polymerization initiator.

12. The curable composition for imprints according to any one of claims 1 and 3 to 6, wherein a ratio of a total mass of the compound C to a total mass of the compound A contained in the composition is 0.2 to 20 mass%.

13. The curable composition for imprints according to any one of claims 1 to 6, wherein the molar amount of the radically polymerizable group relative to the total solid content of the composition is 0.03 to 5.00 mol / g.

14. The curable composition for imprints according to any one of claims 1 to 3, 5 and 6, wherein the compound A has a radical polymerizable group value of 100 to 1,500.

15. The curable composition for imprints according to any one of claims 1 to 4 and 6, wherein the poly(oxyalkylene) group contains an oxyalkylene group represented by the following formula (OA-1): 【Chemistry 5】 In formula (OA-1), R O1 and R O2 each independently represents a hydrogen atom or a methyl group; R O1 and R O2 Both cannot be methyl groups.

16. The curable composition for imprints according to any one of claims 1 to 5, wherein a content of the poly(oxyalkylene) group in compound C is 1 to 50 mass %.

17. A cured product obtained by curing the curable composition for imprints according to any one of claims 1 to 16.

18. Surface free energy is 10 to 70 mJ / m 2 The cured product according to claim 17 ,

19. The cured product according to claim 17 or 18, having a surface elastic modulus of 0.5 to 3.0 GPa.

20. An application step of applying the curable composition for imprints according to any one of claims 1 to 16 to a member to which the composition is to be applied, the member being selected from the group consisting of a support and a mold; a contacting step of contacting a member, which is not selected as the application member from the group consisting of the support and the mold, with the curable composition for imprints as a contact member; a curing step of converting the curable composition for imprints into a cured product; and A peeling step of peeling the mold from the cured product. A method for producing an imprint pattern.

21. The method for producing an imprint pattern according to claim 20 , wherein the support is a member having an adhesive layer on a surface to which the curable composition for imprints is applied.

22. A method for manufacturing a device, comprising the method for manufacturing an imprint pattern according to claim 20 or 21.

Citation Information

Patent Citations

  • Rapid prototyping resin compositions

    EP1757979A1

  • Silicone graft copolymer and its production

    JP2000344829A

  • Thin film pattern forming method

    JP2011104856A

  • Curable composition for nanoimprint and nanoimprint method

    JP2012079865A

  • Functional liquid discharge device, functional liquid discharge method, and imprint system

    JP2012216799A